Medical devices and methods for manufacturing the same

JP7936797B2Active Publication Date: 2026-10-16TERUMO KK
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023531967
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-06-29
Filing Date
2022-06-28
Publication Date
2026-10-16
Estimated Expiration
2042-06-28

Smart Images

  • Figure 0007936797000017
    Figure 0007936797000017
  • Figure 0007936797000018
    Figure 0007936797000018
  • Figure 0007936797000019
    Figure 0007936797000019
Patent Text Reader

Abstract

A purpose of the present invention is to provide technology capable of exhibiting lubrication retention (sliding durability) and flexibility under harsh conditions. The present invention relates to a medical instrument comprising: a base material layer; and a surface lubrication layer formed on at least a portion of the base material layer. The surface lubrication layer contains: a polymer having a carboxyl group or salt thereof, or an ester; and a polyurethane. The polyurethane has an elongation rate of 700% or greater and a Young's modulus of 5.0 N / mm2 or greater.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This invention relates to a medical device and a method for manufacturing the same. [Background technology]

[0002] Medical devices such as catheters, guidewires, and stylets, which are inserted into the lumens and tissues of living bodies such as the airways, trachea, digestive tract, urethra, and blood vessels, require operability that allows for reliable insertion to the target site without damaging the tissue. Furthermore, they must exhibit excellent lubrication to avoid damaging the mucous membrane or causing inflammation due to friction while they are in place within the tissue.

[0003] To satisfy these requirements, it is known to form a coating layer on the substrate surface of a medical device to be inserted into the body, containing a maleic acid-based polymer substance in which the proportion of carboxylic acid esters is adjusted to a predetermined range (for example, International Publication No. 2015 / 029625). [Overview of the Initiative]

[0004] According to the technology disclosed in International Publication No. 2015 / 029625, medical devices can exhibit excellent lubricity even under harsh conditions. On the other hand, in recent years, with the miniaturization and reduction of diameter of medical devices, approaches to treating lesions through very complex biological lumens are becoming more widespread, such as delivering medical instruments to lesion sites through areas with narrow inner diameters or areas with multiple consecutive bends in the biological lumen. Furthermore, with the increasing complexity of medical procedures, the handling of medical devices may take even longer. Therefore, even when treating lesion sites through very complex biological lumens, there is a need for technology that further enhances the lubricity retention (durability) of the surface of medical devices compared to conventional technology in order to maintain good operability of medical devices for a longer period of time. More specifically, under harsh conditions (for example, when delivering medical devices to a lesion site through areas where the radius of bending in a biological lumen is small, areas where bending occurs continuously, or areas where the inner diameter of a biological lumen is narrow), medical devices are required to be flexible enough to conform to the biological lumen in order to deliver the medical device to the desired site. In addition, medical devices are required to have excellent sliding durability, maintaining high lubricity even after repeated sliding of the medical device surface.

[0005] Therefore, the present invention has been made in view of the above circumstances, and aims to provide a technology that can exhibit flexibility (especially tip flexibility) and lubrication retention (sliding durability) even under harsh conditions.

[0006] The inventors conducted diligent research to solve the above problems and, as a result, discovered that the above problems can be solved by combining a polymer having a carboxyl group or a salt or ester thereof with a polyurethane having a specific elongation and Young's modulus, thus completing the present invention.

[0007] In other words, the objective is to provide a medical device comprising a base layer and a surface lubricating layer formed on at least a portion of the base layer, wherein the surface lubricating layer comprises a polymer having a carboxyl group or a salt or ester thereof and polyurethane, and the polyurethane has an elongation of 700% or more and a Young's modulus of 5.0 N / mm².2 The above can be achieved with medical devices. [Brief explanation of the drawing]

[0008] [Figure 1] Figure 1 is a schematic diagram of a lubrication maintenance evaluation test apparatus (friction measuring machine). In Figure 1, 1 represents water; 2 represents a petri dish; 3 represents a sample (medical device); 4 represents a terminal; 5 represents a load; 6 represents a movable table; and 10 represents the friction measuring machine. [Figure 2] Figure 2 illustrates a method for evaluating the presence of hydrophilic polymers and polyurethanes in the surface lubrication layer, as well as their mixing ratio. [Figure 3] Figure 3 is a cross-sectional view showing the tip shape of the Ni-Ti wire used in Example 16 and Comparative Examples 10-11. In Figure 3, 30 represents the Ni-Ti wire; 31 represents the tip; 32 represents the straight tip portion; 33 represents the tapered portion; and 34 represents the rear end. [Figure 4] Figure 4 is a schematic diagram of a micro load cell used for evaluating tip abutment resistance. In Figure 4, 40 represents the micro load cell; 42 represents the load cell; 43 represents the sample; 44 represents the sample chuck; and 46 represents the base. [Figure 5] Figure 5 illustrates the evaluation of guidewire tip reachability using a vascular model. Figure 5A is a plan view showing a part of the vascular model. In Figure 5, 50 represents the vascular model; 51 represents the main vessel; 52 represents the side branches; 53 represents the curved section; and 54 represents the straight section. Figure 5B shows the tip shape of the guidewire used for evaluating guidewire tip reachability using a vascular model. [Figure 6] Figure 6 shows the test system used for particulate matter testing. In Figure 6, 60 represents the test system; 61 represents the hub; 62 represents the catheter tube; and 63 represents the type. [Figure 7] Figure 7 is a schematic partial cross-sectional view showing the laminated surface structure of a typical embodiment of a medical device according to the present invention. In Figure 7, 100 represents the medical device; 101 represents the base layer; and 102 represents the surface lubrication layer. [Figure 8]Figure 8 is a schematic partial cross-sectional view illustrating an example of a different surface lamination configuration as an application example of the embodiment shown in Figure 7. In Figure 8, 100 represents the medical device; 101a represents the substrate layer core; 101b represents the substrate surface layer; and 102 represents the surface lubrication layer. [Modes for carrying out the invention]

[0009] The embodiments for carrying out the present invention will be described in detail below. However, the present invention is not limited to the embodiments described below and can be modified in various ways within the scope of the claims. Throughout this specification, singular expressions should be understood to include the concept of their plural form unless otherwise specified. Therefore, singular articles (e.g., "a," "an," "the" in English) should be understood to include the concept of their plural form unless otherwise specified. Furthermore, terms used in this specification should be understood to have the meaning commonly used in the art unless otherwise specified. Therefore, unless otherwise defined, all technical and scientific terms used in this specification have the same meaning as commonly understood by those skilled in the art to which the present invention pertains. In case of any conflict, this specification (including definitions) shall prevail.

[0010] Furthermore, in this specification, the range "X~Y" includes X and Y, meaning "X or greater and Y or less." In this specification, "A and / or B" means at least one of A and B, and includes both A and B, or either A or B. Unless otherwise specified, operations and measurements of physical properties, etc., are performed under conditions of room temperature (20~25°C) / relative humidity 40~60%RH.

[0011] Furthermore, in this specification, when a constituent unit is defined as "derived from" a monomer, it means that the constituent unit is a divalent constituent unit resulting from the cleavage of one of the polymerizable unsaturated double bonds of the corresponding monomer.

[0012] <Medical devices> A medical device according to one aspect of the present invention comprises a base layer and a surface lubricating layer formed on at least a portion of the base layer, wherein the surface lubricating layer comprises a polymer having a carboxyl group or a salt or ester thereof and polyurethane, and the polyurethane has an elongation of 700% or more and a Young's modulus of 5.0 N / mm². 2 This concludes the explanation. According to the present invention, it is possible to provide a medical device that exhibits flexibility (especially at the tip) and lubrication retention (sliding durability) under harsh conditions.

[0013] Medical devices having the above configuration can exhibit excellent lubricity and lubrication retention (sliding durability) even under harsh conditions (for example, when delivering a medical device to a lesion site through areas where the bending radius of the biological lumen is small, areas where bending sections of the biological lumen are continuous, or areas where the inner diameter of the biological lumen is narrow). Furthermore, medical devices having the above configuration have high flexibility in the surface lubrication layer, which maintains the flexibility of the medical device. Therefore, when the medical device of the present invention is a catheter, the operator can easily follow even complex lesion sites and reach the tip of the medical device to the periphery of the biological lumen. Thus, medical devices having this configuration can be effectively applied to complex lesion sites.

[0014] In this specification, "polymers having carboxyl groups or their salts or esters" are also referred to simply as "hydrophilic polymers" or "hydrophilic polymers according to the present invention." Furthermore, the carboxyl groups or their salts or esters possessed by the hydrophilic polymer are also referred to simply as "carboxylate salts, etc." or "carboxylate salts, etc. according to the present invention."

[0015] In this specification, "an elongation rate of 700% or more and a Young's modulus of 5.0 N / mm²" 2 The polyurethane described above may also be simply referred to as "polyurethane" or "polyurethane according to the present invention."

[0016] In this specification, "severe conditions" refers to a situation in which it is difficult to deliver a medical device to the target site, for example, a situation in which the delivery route from the insertion site to the lesion site (e.g., a biological lumen) contains at least one section that satisfies the following conditions: a small radius of bending, multiple consecutive bends, or a narrow inner diameter. Furthermore, the situation in which "the delivery route from the insertion site to the lesion site (e.g., a biological lumen) contains at least one section that satisfies the following conditions: a small radius of bending, multiple consecutive bends, or a narrow inner diameter" is also simply referred to as a "complex lesion site."

[0017] A preferred embodiment of the medical device according to the present invention will be described below with reference to the attached drawings.

[0018] Figure 7 is a schematic partial cross-sectional view showing the laminated surface structure of a typical embodiment of the medical device according to the present invention (hereinafter also simply referred to as "medical device"). Figure 8 is a schematic partial cross-sectional view showing a different configuration example of the laminated surface structure as an application example of this embodiment. In Figures 7 and 8, 101 represents the base material layer, 101a represents the core portion of the base material layer, 101b represents the base material surface layer, 102 represents the surface lubrication layer, and 100 represents the medical device.

[0019] As shown in Figures 7 and 8, the medical device 100 of this embodiment comprises a base layer 101 and a surface lubricating layer 102 containing a hydrophilic polymer and polyurethane, which is formed (distributed) to cover at least a portion of the surface of the base layer 101 (in the figures, an example is shown where it is formed (distributed) to the entire surface of the base layer 101 in the drawing).

[0020] The following describes the various components of the medical device in this embodiment.

[0021] [Base material layer (base material)] The base layer used in the present invention may be composed of any of the materials and can be appropriately selected according to the application. Specifically, the materials that constitute (form) the base layer 101 include metal materials, polymer materials, ceramics, etc. Here, the base layer 101 may be composed (formed) entirely of any of the above materials, as shown in Figure 7, or it may have a structure in which a base layer core portion 101a composed (formed) of any of the above materials is coated with any of the other above materials in an appropriate manner to constitute (form) the base layer surface layer 101b, as shown in Figure 8. Examples of the latter case include a substrate core portion 101a made of a resin material or the like, on which a metal material is coated by an appropriate method (such as plating, metal vapor deposition, sputtering, or other conventionally known methods) to form a substrate surface layer 101b; or a substrate core portion 101a made of a hard reinforcing material such as a metal material, on which a polymer material that is more flexible than the reinforcing material such as a metal material is coated by an appropriate method (such as dipping, spraying, coating, printing, or other conventionally known methods), or a substrate surface layer 101b is formed by compounding (appropriate reaction treatment) the reinforcing material of the substrate core portion 101a and the polymer material of the substrate surface layer 101b. Therefore, the substrate core portion 101a may be a multilayer structure formed by laminating different materials in multiple layers, or a structure (composite) in which members made of different materials are joined together for each part of the medical device. Furthermore, another middle layer (not shown) may be formed between the substrate core portion 101a and the substrate surface layer 101b. Furthermore, the substrate surface layer 101b may also be a multilayer structure formed by laminating different materials in multiple layers, or a structure (composite) in which components made of different materials are joined together for each part of the medical device.

[0022] The metal material used to form the base layer 101 is not particularly limited, and metal materials commonly used in medical devices such as catheters, stents, and guidewires can be used. Specifically, examples include various stainless steels (SUS) such as SUS304, SUS316, SUS316L, SUS420J2, and SUS630, as well as various alloys such as gold, platinum, silver, copper, nickel, cobalt, titanium, iron, aluminum, tin, and nickel-titanium (Ni-Ti) alloys, nickel-cobalt (Ni-Co) alloys, cobalt-chromium (Co-Cr) alloys, and zinc-tungsten (Zn-W) alloys. These may be used individually or in combination of two or more. The metal material should be appropriately selected to be the most suitable for use as a base layer for catheters, stents, guidewires, etc.

[0023] Furthermore, the polymer material used to constitute (form) the above-mentioned base material layer 101 is not particularly limited, and polymer materials commonly used in medical devices such as catheters, stents, and guidewires are used. Specifically, examples include polyamide resins, polyethylene such as linear low-density polyethylene (LLDPE), low-density polyethylene (LDPE), high-density polyethylene (HDPE), and modified polyethylene, polyolefin resins such as polypropylene, polyester resins such as polyethylene terephthalate (PET), styrene resins such as polystyrene, cyclic polyolefin resins, modified polyolefin resins, epoxy resins, urethane resins, diallyl phthalate resins (allyl resins), polycarbonate resins, fluororesins, amino resins (urea resins, melamine resins, benzoguanamine resins), acrylic resins, polyacetal resins, vinyl acetate resins, phenolic resins, vinyl chloride resins (polyvinyl chloride (PVC)), polytetrafluoroethylene (PTFE), silicone resins (silicon resins), polyether resins such as polyetheretherketone (PEEK), and polyimide resins. Of these, urethane resin, polyvinyl chloride (PVC), and polyethylene terephthalate (PET) are preferred, urethane resin and polyvinyl chloride (PVC) are more preferred, and polyvinyl chloride (PVC) is particularly preferred. The above polymer materials may be used individually or in combination of two or more. For the above polymer materials, the most suitable polymer material for the base layer of catheters, stents, guidewires, etc., should be appropriately selected.

[0024] Furthermore, the shape of the base material layer is not particularly limited and can be appropriately selected depending on the intended use, such as in the form of a sheet, wire, or tube.

[0025] [Surface lubricant layer] The surface lubrication layer in the present invention is formed on at least a portion of the substrate layer and comprises a hydrophilic polymer and polyurethane. Here, the surface lubrication layer does not need to be formed on the entire surface of the substrate layer. It is sufficient for the surface lubrication layer to be formed on the portion of the substrate layer surface that comes into contact with aqueous liquids (e.g., body fluids, blood, physiological saline). The hydrophilic polymer exhibits lubricity when wet (e.g., when in contact with aqueous liquids such as body fluids, blood, or physiological saline; the same applies hereinafter) and physically intertwines (is compatible with) the polyurethane within the surface lubrication layer. The polyurethane according to the present invention has an elongation of 700% or more and a Young's modulus of 5.0 N / mm². 2 This concludes the explanation. Due to these properties, polyurethane can follow the expansion of the hydrophilic polymer when wet, maintaining its film structure. Furthermore, even when the hydrophilic polymer expands when wet, the dissolution of the hydrophilic polymer can be suppressed and prevented. Therefore, the surface lubrication layer according to the present invention can improve lubrication maintenance (sliding durability) under harsh conditions. In addition, polyurethane has appropriate flexibility. For this reason, with the medical device of the present invention, even if there is a complex lesion site, the medical device can be delivered to the periphery of the biological lumen. Moreover, because polyurethane can follow the swelling of the hydrophilic polymer when wet, the surface lubrication layer can secure sufficient space to accommodate aqueous liquids (e.g., body fluids, blood). For this reason, the hydrophilic polymer can come into contact with a sufficient amount of aqueous liquid and exhibit lubrication even under high load conditions.

[0026] The above mechanism is speculative and does not limit the technical scope of the present invention.

[0027] In the present invention, other layers may be present between the surface lubrication layer and the base layer as long as they do not affect the effects of the present invention, but preferably the surface lubrication layer is located directly above the base layer. Also, other layers may be present on top of the surface lubrication layer as long as they do not affect the effects of the present invention, but preferably no other layers are placed on top of the surface lubrication layer (the surface lubrication layer is the outermost layer). With this configuration, the effects of the present invention (e.g., lubrication retention, lubricity) can be effectively exhibited.

[0028] Furthermore, the thickness of the surface lubrication layer is not particularly limited. From the viewpoint of lubricity, durability (lubricity retention), flexibility, and adhesion to adjacent layers (e.g., the substrate layer), the thickness of the surface lubrication layer (dry film thickness) is preferably 0.01 to 20 μm, more preferably 0.1 to 15 μm, and even more preferably 1 to 10 μm.

[0029] (Hydrophilic polymer) The surface lubrication layer according to the present invention contains a polymer (hydrophilic polymer) having a carboxyl group or its salt or ester (carboxylate salt, etc.). When the hydrophilic polymer comes into contact with an aqueous liquid, the carboxylate salt, etc. (for example, an alkali metal salt of a carboxyl group) present in the hydrophilic polymer swells and gels in the aqueous liquid, exhibiting lubrication.

[0030] Here, examples of hydrophilic polymers include hyaluronic acid or its alkali metal salts or group 2 metal salts, polyacrylic acid or its alkali metal salts or group 2 metal salts, polymers having the structural unit shown in formula (1) below, alginic acid or its alkali metal salts or group 2 metal salts, carboxymethylcellulose or its alkali metal salts or group 2 metal salts, xanthan gum or its alkali metal salts or group 2 metal salts. Of these, hyaluronic acid or its alkali metal salts or group 2 metal salts, polyacrylic acid or its alkali metal salts or group 2 metal salts, and polymers having the structural unit shown in formula (1) below are preferred, polyacrylic acid or its alkali metal salts or group 2 metal salts, and polymers having the structural unit shown in formula (1) below are more preferred, and polymers having the structural unit shown in formula (1) below are particularly preferred. These hydrophilic polymers can exhibit higher lubricity (sliding durability) under harsh conditions. Furthermore, these hydrophilic polymers can exhibit higher lubricity when in contact with aqueous liquids.

[0031] [ka]

[0032] The surface lubrication layer may contain the hydrophilic polymer alone, or it may contain two or more hydrophilic polymers.

[0033] That is, in a preferred embodiment of the present invention, the polymer (hydrophilic polymer) is at least one selected from the group consisting of hyaluronic acid or its alkali metal salts or group 2 metal salts, polyacrylic acid or its alkali metal salts or group 2 metal salts, and polymers having the structural unit represented by formula (1) above. In a more preferred embodiment of the present invention, the polymer (hydrophilic polymer) is at least one selected from the group consisting of polyacrylic acid or its alkali metal salts or group 2 metal salts, and polymers having the structural unit represented by formula (1) above. In a particularly preferred embodiment of the present invention, the polymer (hydrophilic polymer) is a polymer having the structural unit represented by formula (1) above.

[0034] Examples of alkali metal salts or group 2 metal salts of hyaluronic acid include potassium salt, sodium salt, calcium salt, lithium salt, and magnesium salt of hyaluronic acid. Note that in alkali metal salts or group 2 metal salts of hyaluronic acid, all carboxyl groups may be in the form of a salt, or some carboxyl groups may be in the form of a salt. Preferably, in alkali metal salts or group 2 metal salts of hyaluronic acid, all carboxyl groups are in the form of a salt. From the viewpoint of higher lubricity retention (sliding durability) and higher lubricity when in contact with aqueous liquids, sodium hyaluronate and potassium hyaluronate are preferred, with sodium hyaluronate being more preferred.

[0035] Examples of the alkali metal salt or Group 2 metal salt of polyacrylic acid include potassium salt, sodium salt, calcium salt, and magnesium salt of polyacrylic acid. Regarding the alkali metal salt or Group 2 metal salt of polyacrylic acid, all carboxyl groups may be in the form of a salt, or a part of the carboxyl groups may be in the form of a salt. Preferably, in the alkali metal salt or Group 2 metal salt of polyacrylic acid, all carboxyl groups are in the form of a salt. From the viewpoints of higher lubrication retention property (sliding durability), higher lubricity upon contact with an aqueous liquid, and the like, sodium polyacrylate and potassium polyacrylate are preferred, and sodium polyacrylate is more preferred.

[0036] An embodiment in which the hydrophilic polymer is a polymer having a structural unit represented by the following formula (1) will be described.

[0037]

Chemical Formula

[0038] In the above formula (1), X 1 and X 2 each independently represent a hydrogen atom, an alkali metal, a Group 2 metal, or a linear or branched alkyl group having 1 to 24 carbon atoms. In this case, X 1 and X 2 may each be the same or different. Here, examples of the alkali metal include lithium, sodium, potassium, rubidium, and cesium. Examples of the Group 2 metal include magnesium, calcium, strontium, and barium. Note that, when X 1 or X 2 is a Group 2 metal, adjacent carboxyl groups are linked via X 1 or X 2 (-C(=O)-O-(X 1 or X 2)-OC(=O)-). Also, examples of linear or branched alkyl groups having 1 to 24 carbon atoms include methyl group, ethyl group, propyl group, isopropyl group, butyl group, isobutyl group, sec-butyl group, tert-butyl group, pentyl group, isopentyl group, tert-pentyl group, neopentyl group, hexyl group, isohexyl group, heptyl group, octyl group, nonyl group, decyl group, undecyl group, dodecyl group, 2-ethylhexyl group, tridecyl group, tetradecyl group, pentadecyl group, hexadecyl group, heptadecyl group, octadecyl group, nonadecyl group, eicosyl group, heneicosyl group, docosyl group, etc. Of these, from the viewpoint of lubricity maintenance and improvement of lubricity, X 1 and X 2 Each of these is preferably independently sodium, potassium, magnesium, calcium, or a linear or branched alkyl group having 1 to 8 carbon atoms, more preferably sodium, calcium, or a linear or branched alkyl group having 1 to 3 carbon atoms, and particularly preferably sodium or an ethyl group. From the viewpoint of lubrication maintenance and improved lubricity, X 1 and X 2 Preferably, at least one of them is an alkali metal or a linear or branched alkyl group having 1 to 8 carbon atoms, X 1 and X 2 It is more preferable that one of them is sodium or potassium and the other is a linear or branched alkyl group having 1 to 3 carbon atoms, X 1 and X 2 It is particularly preferable that one of them is sodium and the other is an ethyl group. 1 and X 2 If one of the components is sodium, when a hydrophilic polymer comes into contact with an aqueous liquid, the sodium ion dissociates in the aqueous liquid, and the hydrophilic carboxyl group becomes negatively charged (-COO -(This results in...). As a result, an ion concentration difference is created between the hydrophilic polymer and the aqueous liquid, and water molecules are easily incorporated into the polymer. At the same time, since the hydrophilic groups are in anionic form, Coulomb repulsion acts between the hydrophilic groups, and the network structure formed by the hydrophilic polymer becomes larger in the aqueous liquid, allowing it to incorporate more water molecules (and swell more). Therefore, hydrophilic polymers can exhibit particularly excellent lubricity and lubrication retention. Note that X 1 or X 2 The form in which is an alkali metal or a group 2 metal is X 1 and X 2 It is obtained by alkali treatment of a polymer in which hydrogen atoms are present. Specifically, alkali treatment is performed, for example, X 1 and X 2 This can be done by adding an alkali such as sodium bicarbonate to a polymer solution in which hydrogen atoms are present. A coating liquid that forms a lubricating layer may be prepared using the hydrophilic polymer obtained as described above. Alternatively, as described in WO2015 / 029625, X 1 and X 2 A lubricating layer may be formed using a polymer in which hydrogen atoms are present, followed by alkaline treatment using an alkali such as sodium bicarbonate.

[0039] The constituent unit represented by formula (1) above may be a single constituent unit represented by formula (1) above, or it may be two or more constituent units represented by formula (1) above. Preferably, the constituent unit represented by formula (1) above is a single constituent unit represented by formula (1) above. In the latter case, the multiple constituent units may exist in a block-like manner or in a random manner. For example, constituent unit (1) may be X as described in WO2015 / 029625. 1 However, X represents a hydrogen atom, an alkali metal, or a Group 2 metal. 2 The constituent units (a) of the above formula (1) represent linear or branched alkyl groups having 1 to 24 carbon atoms, and X 1 and X 2However, each is independently composed of a constituent unit (b) of the above formula (1) representing a hydrogen atom, an alkali metal, or a group 2 metal, and in this case, the composition of constituent unit (a):constituent unit (b) may be 100:2 to 100:50 (preferably 100:2 to 100:43) (molar ratio). Note that this composition is substantially equivalent to the ratio of the amount of monomers corresponding to each constituent unit to the total amount of monomers charged (moles) of all monomers when manufacturing the polymer.

[0040] Furthermore, a polymer having the structural unit shown in formula (1) above may also have structural units derived from other monomers (other structural units) in addition to the structural unit shown in formula (1). The other monomers are not particularly limited as long as they do not hinder the effects of the present invention (e.g., lubricity maintenance under harsh conditions). Specifically, examples include monomers having alkyl vinyl ethers, acrylamides and their derivatives, vinylpyrrolidones, acrylic acids and methacrylic acids and their derivatives, diene compounds, sugars, and phospholipids as side chains. More specifically, examples include methyl vinyl ether, ethyl vinyl ether, propyl vinyl ether, acrylic acid, methacrylic acid, N-methylacrylamide, N,N-dimethylacrylamide, acrylamide, acryloylmorpholine, N,N-dimethylaminoethyl acrylate, vinylpyrrolidone, 2-methacryloyloxyethyl phospholylcholine, 2-methacryloyloxyethyl-D-glycoside, 2-methacryloyloxyethyl-D-mannoside, vinyl methyl ether, and hydroxyethyl methacrylate. Of these, alkyl vinyl ethers are preferred, methyl vinyl ether and ethyl vinyl ether are more preferred, and methyl vinyl ether is particularly preferred, considering lubricity in wet conditions, lubricity in wet conditions under harsh conditions, and lubrication maintenance. Furthermore, it is preferable that the hydrophilic polymer substantially does not contain the maleic anhydride-derived structural units of the following structure. Here, "the hydrophilic polymer substantially contains no maleic anhydride-derived structural units" means that the content of maleic anhydride-derived structural units in the structure shown below is less than 5 mol% (lower limit: 0 mol%) of the total structural units. The presence or absence of maleic anhydride-derived structural units can be confirmed by infrared spectroscopy.

[0041] [ka]

[0042] In one embodiment of the present invention, the hydrophilic polymer comprises the structural unit represented by formula (1) and the structural unit derived from alkyl vinyl ether (-2HC-CH(OX 3It is a copolymer composed of )-). Here, the formula representing the constituent unit derived from alkyl vinyl ether is:-2HC-CH(OX 3 )- in X 3 X is a linear or branched alkyl group having 1 to 24 carbon atoms. Here, the definition of "linear or branched alkyl group having 1 to 24 carbon atoms" is the same as that of the alkyl group in formula (1) above, so the explanation is omitted here. Of these, X 3 The alkyl group is preferably a linear or branched alkyl group having 1 to 8 carbon atoms, more preferably a linear or branched alkyl group having 1 to 3 carbon atoms, even more preferably a methyl group or an ethyl group, and particularly preferably a methyl group (i.e., the other constituent units are represented by the formula: -2HC-CH(OCH3)-). In this embodiment, the copolymer has the following structure, consisting of the constituent unit represented by the above formula (1) and the constituent unit derived from the alkyl vinyl ether (-2HC-CH(OX 3 The structure may consist of )-) as one constituent unit. Alternatively, each constituent unit may be block-shaped or random.

[0043] [ka]

[0044] When the hydrophilic polymer is a copolymer composed of the constituent units shown in formula (1) and constituent units derived from other monomers (other constituent units, particularly those derived from alkyl vinyl ethers; the same applies hereinafter), the composition of each constituent unit (the monomer that forms each constituent unit) is not particularly limited and is appropriately selected considering the desired effect (e.g., lubricity maintenance and lubricity under harsh conditions). Specifically, the hydrophilic polymer is preferably composed of 20 to 80 mol% of the constituent units shown in formula (1) and 80 to 20 mol% of other constituent units, more preferably 30 to 70 mol% of the constituent units shown in formula (1) and 70 to 30 mol% of other constituent units, and particularly preferably 45 to 55 mol% of the constituent units shown in formula (1) and 55 to 45 mol% of other constituent units. Here, the total amount of the constituent units shown in formula (1) and other constituent units is 100 mol%. Furthermore, this composition is substantially equivalent to the ratio of the amount of monomers (moles) corresponding to each constituent unit to the total amount (moles) of monomers used when manufacturing the polymer.

[0045] Hydrophilic polymers may also have an insoluble form, as long as they have degrees of freedom in their molecular chains and can take on a hydrated form. Such forms are not particularly limited, as long as they have degrees of freedom in their molecular chains and can take on a hydrated form. Specifically, examples include amidates, anhydrides, halides, ethers, hydrolysates, acetals, formalides, alkylolates, quaternaries, diazotes, hydrazides, sulfons, nitrates, ion complexes, and crosslinks with substances having two or more reactive functional groups, such as diazonium groups, azides, isocyanates, acid chloride groups, acid anhydrides, iminocarbonates, amino groups, carboxyls, epoxy groups, hydroxyls, and aldehydes, obtained by condensation, addition, substitution, oxidation, and reduction reactions of the hydrophilic polymers. Such hydrophilic polymers, when brought into contact with bodily fluids or blood, can significantly reduce frictional resistance with biological tubules and tissues, making them suitable for use as lubricants. Derivatives obtained by condensation, addition, or substitution reactions of these hydrophilic polymers, as well as those partially crosslinked, are similarly effective as lubricants.

[0046] In a preferred embodiment of the present invention, the hydrophilic polymer has the following constituent units. In a more preferred embodiment of the present invention, the hydrophilic polymer is composed of the following constituent units.

[0047] [ka]

[0048] In a particularly preferred embodiment of the present invention, the hydrophilic polymer has the following constituent units. In a more preferred embodiment of the present invention, the hydrophilic polymer is composed of the following constituent units.

[0049] [ka]

[0050] The molecular weight of the hydrophilic polymer is appropriately selected considering the desired effect (e.g., lubrication retention under harsh conditions, lubricity). Specifically, the weight-average molecular weight (Mw) of the hydrophilic polymer is preferably 10,000 to 7 million, more preferably 100,000 to 5 million. In this specification, the molecular weight (weight-average molecular weight) of the hydrophilic polymer is measured by gel permeation chromatography (GPC) using polystyrene as the standard substance and tetrahydrofuran (THF) as the mobile phase. The molecular weight of the hydrophilic polymer can also be calculated based on the type and number of repeating units.

[0051] (Polyurethane) The surface lubrication layer according to the present invention includes polyurethane in addition to the polymer having a carboxyl group or its salt or ester (hydrophilic polymer). Here, the polyurethane has an elongation of 700% or more and a Young's modulus of 5.0 N / mm². 2That concludes the explanation. Normally, hydrophilic polymers dissolve in water. Therefore, when wet (for example, when in contact with aqueous liquids such as bodily fluids, blood, or saline solution), the hydrophilic polymer gradually dissolves, reducing lubrication retention (sliding durability). In contrast, polyurethane has an appropriate balance of flexibility (elongation) and hardness (Young's modulus) and exhibits high compatibility with hydrophilic polymers. When polyurethane is combined with a hydrophilic polymer, the hydrophilic polymer and polyurethane (especially the soft segment portion) physically intertwine (become compatible) on a nano-order (without undergoing a chemical reaction) within the surface lubrication layer. This suppresses the dissolution of the hydrophilic polymer when wet (for example, when in contact with bodily fluids or blood). Furthermore, polyurethane has the specific elongation (flexibility) described above. Therefore, even if the hydrophilic polymer absorbs and swells with a large amount of aqueous liquid when wet, the polyurethane has the elasticity to withstand the expansion and can follow the expansion (swelling) of the hydrophilic polymer well. Therefore, when the surface lubrication layer comes into contact with the wall of a living lumen such as a blood vessel, a sufficient amount of aqueous liquid seeps out onto the surface of the surface lubrication layer, preventing contact between the medical device and the living lumen wall. As a result, the surface lubrication layer can exhibit excellent lubrication even under harsh conditions. Furthermore, because polyurethane is flexible, the flexibility of the medical device itself equipped with the surface lubrication layer can be maintained. When the medical device equipped with the surface lubrication layer according to the present invention is a catheter or a guidewire, the flexibility of the tip of the catheter or guidewire can be maintained (low tip abutment resistance). As a result, when the operator manipulates the medical device according to the present invention (for example, a catheter or a guidewire), it can easily pass through areas where the living lumen is strongly bent (small bending radius) or where there are multiple consecutive bends, allowing the tip of the catheter or guidewire to reach the periphery of the living lumen. In addition, because the surface lubrication layer contains polyurethane having a specific Young's modulus (hardness) as described above, the surface lubrication layer has a certain level of film strength (especially near the interface with the base layer). Therefore, the surface lubrication layer is less likely to peel off the base layer even when subjected to repeated sliding friction (for example, in areas with multiple consecutive bends) or when passing through narrow areas, thus maintaining its film structure.Therefore, the surface lubrication layer according to the present invention can improve lubrication retention (sliding durability) under harsh conditions. However, the above mechanism is speculative and does not limit the technical scope of the present invention.

[0052] Polyurethane has an elongation rate of over 700% and a load capacity of 5.0 N / mm². 2 It has the above Young's modulus. Here, if the elongation of the polyurethane is less than 700%, it will not be able to adequately respond to the absorption and swelling of aqueous liquids in the hydrophilic polymer, and the lubricity will decrease. Also, the Young's modulus of the polyurethane is 5.0 N / mm². 2 If the elongation is less than 700%, the film strength will be weak, and the film structure cannot be maintained against repeated sliding friction (for example, in areas with multiple consecutive bends) or when passing through narrow areas. As a result, lubrication retention (sliding durability) will decrease. As a result, the hydrophilic polymer will dissolve when wet. Also, if the hydrophilic polymer absorbs and swells a large amount of aqueous liquid when wet, it will not be able to keep up with the swelling, and the film structure of the surface lubrication layer will be destroyed. As a result, surface lubrication layers using such polyurethane have poor lubrication retention (sliding durability) under harsh conditions. From the viewpoint of improving lubrication retention (sliding durability) under harsh conditions and flexibility, the elongation of the polyurethane is preferably greater than 700%, more preferably greater than 1000%, even more preferably greater than 1100%, and particularly preferably greater than 1100%. The upper limit of the elongation of the polyurethane is, for example, 3000% or less, and preferably 2000% or less. Furthermore, from the viewpoint of improving lubrication retention (sliding durability) under harsh conditions and film strength, the Young's modulus of polyurethane is preferably 5.0 N / mm². 2 More preferably 5.2 N / mm 2 Exceeding 5.4 N / mm², and particularly preferably 5.4 N / mm² 2 That concludes the explanation. Note that the upper limit of the Young's modulus of polyurethane is, for example, 800 N / mm². 2 The following, preferably 320 N / mm 2 The following, and more preferably 300 N / mm 2 It is less than 50 N / mm², and is particularly preferably 50 N / mm². 2 It is less than.

[0053] In other words, in a preferred embodiment of the present invention, the polyurethane has an elongation of more than 700% and a Young's modulus of 5.0 N / mm². 2 In a more preferred embodiment of the present invention, the polyurethane has an elongation of more than 1000% and a Young's modulus of 5.2 N / mm². 2 In a more preferred embodiment of the present invention, the polyurethane has an elongation of 1100% or more and a Young's modulus of 5.4 N / mm². 2 That concludes the explanation. In a particularly preferred embodiment of the present invention, the polyurethane has an elongation of more than 1100% and a Young's modulus of 5.4 N / mm². 2 That's all.

[0054] The surface lubrication layer contains a large amount of hydrophilic polymer when wet. aqueous When polyurethane absorbs and swells with liquid, it also expands and contracts, deforming along with the liquid. For this reason, the polyurethane in the surface lubrication layer contains a large amount of hydrophilic polymer when wet. aqueous When a liquid is absorbed and swells, materials that deform due to the swelling of the hydrophilic polymer are preferred. In other words, polyurethanes that exhibit low stress when subjected to external force are preferred. From this viewpoint, the 100% modulus of polyurethane is preferably 6.9 N / mm². 2 Less than, more preferably 6.2 N / mm² 2 More preferably, 6.2 N / mm 2 Less than, and more preferably 3.0 N / mm² 2 The following, and especially preferably 2.5 N / mm 2 It is less than [value]. Note that the lower limit of the 100% modulus of polyurethane is, for example, 0.5 N / mm². 2 The above is preferable, and preferably 0.7 N / mm 2 That concludes the explanation. With polyurethane having a 100% modulus within this range, even if the hydrophilic polymer absorbs and swells with a large amount of aqueous liquid when wet, it will deform together and be able to follow the swelling of the hydrophilic polymer well. Therefore, the surface lubrication layer can exhibit excellent lubrication retention (durability) and flexibility even under harsh conditions.

[0055] In other words, in a preferred embodiment of the present invention, the polyurethane has an elongation of more than 700% and a Young's modulus of 5.0 N / mm². 2 It exceeds 100% modulus of 6.9 N / mm 2 It is less than. In a more preferred embodiment of the present invention, the polyurethane has an elongation of more than 1000% and a Young's modulus of 5.2 N / mm². 2 It exceeds 100% modulus of 6.2 N / mm 2 The following is a more preferred embodiment of the present invention: In a more preferred embodiment of the present invention, the polyurethane has an elongation of more than 1000% and a Young's modulus of 5.2 N / mm². 2 It exceeds 100% modulus of 6.2 N / mm 2 It is less than. In a more preferred embodiment of the present invention, the polyurethane has an elongation of 1100% or more and a Young's modulus of 5.4 N / mm². 2 The above is the result, and the 100% modulus is 3.0 N / mm². 2 The following is a particularly preferred embodiment of the present invention: In the polyurethane, the elongation exceeds 1100% and the Young's modulus is 5.4 N / mm². 2 The above is the result, with a 100% modulus of 2.5 N / mm². 2 It is less than.

[0056] In this specification, the elongation, Young's modulus, and 100% modulus of polyurethane are those values ​​obtained according to the following method.

[0057] (Measurement of elongation, Young's modulus, and 100% modulus) A solution containing dissolved or dispersed polyurethane is placed in a Teflon® coated petri dish to a film thickness of 500 μm. The film is dried at room temperature (25°C) for 15 hours, at 80°C for 6 hours, and at 120°C for 20 minutes to form a coating. The resulting coating is cut into dumbbell-shaped test pieces (No. 3) to prepare a sample. This sample is then tested using a Tensilon universal material tester (manufactured by Orientec Co., Ltd.) in accordance with JIS K6251:2017 (formerly JIS K6301) at a tensile speed of 200 mm / min to determine elongation (%) and Young's modulus (N / mm²). 2 ) and 100% modulus (N / mm²) 2The elongation rate is measured. The elongation rate is the ratio of the elongation at the time of fracture of the test specimen to the original length of the test specimen, expressed as a percentage. Young's modulus indicates the relationship between stress and strain in the elastic region (initial proportional region) of the material, and is the value obtained by dividing the tensile stress when the test specimen is pulled by the change (strain) relative to the original length of the test specimen. 100% modulus is the tensile stress when the elongation rate of the test specimen is 100%.

[0058] Polyurethane is a reaction product of an isocyanate compound having an isocyanate group (NCO group) and a polyhydric alcohol having two or more hydroxyl groups (OH groups) in one molecule, and has a soft segment and a hard segment. Examples of polyurethanes include ester / ether-based polyurethanes, ether-based polyurethanes, ester-based polyurethanes, carbonate-based polyurethanes, and acrylic-based polyurethanes. Polyurethane may be used alone or in combination of two or more types.

[0059] The isocyanate compounds that form polyurethane are organic compounds (polyvalent isocyanate compounds) having two or more isocyanate groups in one molecule. Examples of isocyanate compounds include aliphatic isocyanates, alicyclic isocyanates, and aromatic isocyanates.

[0060] Specific examples of aliphatic isocyanate compounds include 1,6-hexamethylene diisocyanate (HDI).

[0061] Specific examples of alicyclic isocyanate compounds include dicyclohexylmethane diisocyanate, isophorone diisocyanate (IPDI), 1,3-cyclohexane diisocyanate, and 1,4-cyclohexane diisocyanate.

[0062] Examples of aromatic isocyanate compounds include 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, 4,4'-diphenylmethane diisocyanate, 2,4'-diphenylmethane diisocyanate, 2,2'-diphenylmethane diisocyanate, xylylene diisocyanate (XDI), and naphthylene diisocyanate (NDI).

[0063] These isocyanate compounds may be used individually or in combination of two or more.

[0064] Among isocyanate compounds, aliphatic or alicyclic isocyanate compounds are preferred, with 1,6-hexamethylene diisocyanate (HDI) and isophorone diisocyanate (IPDI) being more preferred.

[0065] The content of constituent units derived from isocyanate compounds is preferably more than 3 mol% and less than 25 mol%, more preferably 5 to 18 mol%, relative to the total constituent units of polyurethane.

[0066] Specific examples of polyhydric alcohols include low molecular weight diols such as ethylene glycol, propylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, neopentyl glycol, diethylene glycol, trimethylene glycol, triethylene glycol, tetraethylene glycol, dipropylene glycol, tripropylene glycol, hexanediol, and cyclohexanedimethanol; low molecular weight compounds having three or more hydroxyl groups such as glycerin, trimethylolpropane (TMP), and pentaerythritol; and at least one of the above low molecular weight diols mixed with ethylene oxide, propylene oxide, etc. Polyether diols obtained by addition polymerization of tetrahydrofuran, etc.; compounds having a hydroxyl group and a carboxyl group in one molecule, such as dimethylolpropionic acid and dimethylolbutanoic acid; polyester diols obtained by polycondensation of at least one low molecular weight diol with dicarboxylic acids such as adipic acid, sebacic acid, itaconic acid, maleic anhydride, terephthalic acid, and isophthalic acid; polyether diols such as polyethylene glycol, polypropylene glycol, and polytetramethylene ether diol; and other examples include 6-hydroxyhexanoic acid, polycaprolactone diol, polycarbonate diol, polybutadiene diol, hydrogenated polybutadiene diol, and polyacrylic acid ester diol. A single polyhydric alcohol may be used alone, or two or more may be used in combination.

[0067] From the viewpoint of improving compatibility and flexibility, it is preferable that the polyhydric alcohol contains a polyetherdiol.

[0068] The content of polyhydric alcohol-derived structural units is preferably more than 75 mol% and less than 97 mol%, and more preferably 82 to 95 mol%, relative to the total structural units of polyurethane.

[0069] It is preferable that the polyurethane has ethylene oxide-derived structural units (-CH2CH2O- or -OCH2CH2-) as soft segments. This allows for even higher control of the polyurethane's flexibility (elongation). It also improves compatibility with hydrophilic polymers. Here, the content of ethylene oxide-derived structural units is preferably more than 15 mol% and less than 45 mol%, and more preferably more than 20 mol% and less than 40 mol%, relative to the total structural units of the polyurethane. A polyurethane having ethylene oxide-derived structural units in such amounts in its soft segments can exhibit higher flexibility (elongation). It also exhibits better compatibility with hydrophilic polymers. Therefore, by using such a polyurethane, lubricity retention (sliding durability) and flexibility can be further improved.

[0070] As a method for producing polyurethane, known methods can be used in the same manner or with appropriate modifications, such as reacting the polyhydric alcohol compound and the isocyanate compound in an ether such as dioxane using a catalyst such as dibutyltin dilaurate.

[0071] The weight-average molecular weight (Mw) of polyurethane is preferably 100,000 or more. Furthermore, it is preferable that the weight-average molecular weight of polyurethane be 5,000,000 or less. Here, the "weight-average molecular weight" is measured by dissolving the polyurethane (sample) in a suitable solvent and using polystyrene as a standard substance, then measuring it by gel permeation chromatography (GPC). Note that the molecular weight of polyurethane can also be calculated based on the type and number of repeating units.

[0072] Polyurethane may be used in a form dispersed in water (in the form of a polyurethane aqueous dispersion). In this case, the polyurethane content (solid content concentration) in the polyurethane aqueous dispersion is, for example, 80% by mass or less, preferably 70% by mass or less, and more preferably 60% by mass or less. Alternatively, the polyurethane content (solid content concentration) in the polyurethane aqueous dispersion is, for example, 10% by mass or more, preferably 20% by mass or more, and more preferably 25% by mass or more. In one embodiment of the present invention, the polyurethane content in the polyurethane aqueous dispersion is 10 to 80% by mass, preferably 20 to 70% by mass, and more preferably 25 to 60% by mass.

[0073] When polyurethane is used in a form dispersed in water, the average particle size (diameter) of the polyurethane in the aqueous polyurethane dispersion is preferably greater than 50 nm, more preferably greater than 60 nm, and particularly preferably greater than 60 nm. Furthermore, the average particle size (diameter) of the polyurethane in the aqueous polyurethane dispersion is preferably 1000 nm or less, more preferably 800 nm or less, and particularly preferably 700 nm or less. In other words, the average particle size of the polyurethane in the aqueous polyurethane dispersion is preferably greater than 50 nm and 1000 nm or less, more preferably between 60 and 800 nm, and particularly preferably greater than 60 nm and 700 nm or less. In this specification, the average particle size (diameter) of the polyurethane in the aqueous polyurethane dispersion is the value of the harmonic mean particle size (nm) based on scattered light intensity calculated by cumulant analysis using a nanotrack particle size distribution analyzer UPA-EX150 (manufactured by Nikkiso Co., Ltd.) using the light scattering method at room temperature.

[0074] As the aqueous dispersion of polyurethane resin described above, commercially available aqueous polyurethane polymer dispersions (polyurethane dispersions: PUDs) can be used as is. Specifically, Superflex® 300 (non-yellowing isocyanate ester / ether-based polyurethane, elongation: 1500%, Young's modulus: 5.4 N / mm²) can be used. 2 100% Modulus: 1.7 N / mm 2(EO content: over 20 mol%, weight-average molecular weight: over 100,000, average particle size in aqueous dispersion: 70 nm), Superflex (registered trademark) 500M (non-yellowing isocyanate ester polyurethane, elongation: 1100%, Young's modulus: 319 N / mm²) 2 100% Modulus: 6.2 N / mm 2 (EO content: over 20 mol%, weight-average molecular weight: over 100,000, average particle size in aqueous dispersion: 140 mm), Superflex (registered trademark) E-2000 (non-yellowing isocyanate ester polyurethane, elongation: 1350%, Young's modulus: 11 N / mm) 2 100% Modulus: 0.7 N / mm 2 , etc. (EO content: over 20 mol%, weight-average molecular weight: 100,000 or more, average particle size in aqueous dispersion: 700 nm) (all manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) can be used.

[0075] Polyurethane or polyurethane aqueous dispersions may be used individually or in combination of two or more types.

[0076] The mixing ratio of polyurethane to hydrophilic polymer in the surface lubrication layer is, for example, preferably 50 to 1200 parts by mass, more preferably 100 to 1000 parts by mass, and particularly preferably 200 to 600 parts by mass of polyurethane per 100 parts by mass of hydrophilic polymer. With such a mixing ratio, the hydrophilic polymer and polyurethane are more compatible, and the elution of the hydrophilic polymer when in contact with aqueous liquid can be more effectively suppressed and prevented (the lubrication maintenance (sliding durability) can be further improved). That is, in a preferred embodiment of the present invention, polyurethane is included in the surface lubrication layer at a ratio of 50 to 1200 parts by mass per 100 parts by mass of polymer (hydrophilic polymer). In a more preferred embodiment of the present invention, polyurethane is included in the surface lubrication layer at a ratio of 100 to 1000 parts by mass per 100 parts by mass of polymer (hydrophilic polymer). In a particularly preferred embodiment of the present invention, polyurethane is included in the surface lubrication layer at a ratio of 200 to 600 parts by mass per 100 parts by mass of polymer (hydrophilic polymer). Here, the presence of hydrophilic polymers and polyurethanes in the surface lubrication layer, as well as their mixing ratio, can be confirmed and measured using known analytical methods such as FT-IR, XPS, and TOF-SIMS. For example, the presence of hydrophilic polymers and polyurethanes in the surface lubrication layer, as well as their mixing ratio, can be confirmed by performing FT-IR measurements before and after irradiation with active energy rays and comparing the ratio of the peak of bonds formed by active energy ray irradiation to the peak of bonds that remain unchanged.

[0077] In this specification, the presence of hydrophilic polymers and polyurethanes in the surface lubrication layer, as well as their mixing ratio, are evaluated by FT-IR using an FT-IR spectrophotometer (Nicolet iS50, Thermo Fisher Scientific). Specifically, the surface lubrication layer or a medical device containing the surface lubrication layer is placed on a sample stage and surface analysis is performed by ATR-IR. In the resulting IR chart, 1570 cm² -1 The peaks in the vicinity indicate C=O stretching vibrations caused by carboxylates, etc. Also, 1530 cm -1The peaks in the vicinity show polyurethane-induced CNH bending vibrations. For example, in the IR chart in Figure 2, at 1570 cm -1 If a nearby peak ("Peak A" in Figure 2) is observed, it indicates that the surface lubrication layer contains a hydrophilic polymer. Also, at 1530 cm -1 The presence of a nearby peak ("Peak B" in Figure 2) indicates that the surface lubrication layer contains polyurethane.

[0078] Furthermore, in Figure 2, find the intersection point ("Intersection Point A" in Figure 2) of the tangent line A connecting valleys A and A' located to the left and right of peak A, and the line drawn perpendicularly from peak A. Next, calculate the distance (X) between peak A and intersection point A. A Measure the distance (mm). Similarly, find the intersection point ("Intersection Point B" in Figure 2) of the tangent line B connecting valleys B and B' located to the left and right of peak B, and the line drawn perpendicularly from peak B. Next, calculate the distance (X) between peak B and intersection B. B Measure the distance (X) in (mm). A (mm) and distance (X B Based on (mm), the mixing ratio of hydrophilic polymer and polyurethane in the surface lubrication layer (mixing ratio of polyurethane to 100 parts by mass of polymer (hydrophilic polymer)) is calculated using the following formula (A).

[0079]

number

[0080] As described above, by using a combination of polyurethane with specific elongation and Young's modulus and a hydrophilic polymer, the surface lubrication layer can exhibit higher lubrication retention (sliding durability) and flexibility under harsh conditions. Furthermore, such a surface lubrication layer can exhibit higher lubricity when in contact with aqueous liquids under harsh conditions.

[0081] (Other ingredients) The surface lubrication layer may consist solely of hydrophilic polymers and polyurethanes, or it may further contain other components in addition to the hydrophilic polymers and polyurethanes.

[0082] In one embodiment of the present invention, the surface lubrication layer is substantially composed of a hydrophilic polymer and polyurethane. Here, "the surface lubrication layer is substantially composed of a hydrophilic polymer and polyurethane" means that the total content (in terms of solids) of the hydrophilic polymer and polyurethane in the surface lubrication layer is greater than 95% by mass (upper limit: 100% by mass).

[0083] Furthermore, in one embodiment of the present invention, the surface lubrication layer is composed of a hydrophilic polymer and polyurethane (total content of hydrophilic polymer and polyurethane in the surface lubrication layer (in terms of solid content) = 100% by mass).

[0084] Furthermore, in one embodiment of the present invention, the surface lubrication layer comprises a hydrophilic polymer, polyurethane, and other components. In this embodiment, the other components are preferably polyisocyanates. The polyisocyanates crosslink each isocyanate group to form self-crosslinked structures. These self-crosslinked structures also physically intertwine (become compatible) with the hydrophilic polymer in the surface lubrication layer. Therefore, the elution of the hydrophilic polymer can be further suppressed and prevented when the hydrophilic polymer expands due to wetting. In addition, if the material constituting the base layer has active hydrogen, it can be linked to the base layer via the polyisocyanate. Thus, by coexisting with polyisocyanates, the lubrication retention (durability) under harsh conditions can be further improved. That is, in a preferred embodiment of the present invention, the surface lubrication layer further comprises polyisocyanates or their crosslinked structures. In this specification, "crosslinked polyisocyanates" refers to structures in which each isocyanate group (-N=C=O) of the polyisocyanate is self-crosslinked, or structures that bond with active hydrogen present in the base layer.

[0085] Polyisocyanates may be synthesized using known methods or commercially available products may be used. Examples of commercially available products include the Elastron® series (e.g., BN-69, BN-77, BN-27, BN-04) (manufactured by Daiichi Kogyo Seiyaku Co., Ltd.); LuxateHC series (e.g., 1170, 2170) (manufactured by Orin Chemicals Corporation); Coronate series (e.g., BI-301, 2507, 2554, 2512, 2513, 2515, 2520) (manufactured by Tosoh Corporation); and Barno. **D-500, D-550, DB-980K** (manufactured by DIC Corporation); **Takenate Series** (manufactured by Mitsui Chemicals, Inc.) 1100, BL-1265), Desmodule series (e.g., TPLS-2957, TPLS-2062, TPLS-2078, TPLS-2117), Desmoserm series (e.g., 2170, 2265), Bihijule series (e.g., BL5140, BL5235) (all manufactured by Sumika Covestro Urethane Co., Ltd.); Block Isocyanate series (e.g., 7950, 79 Examples include 51, 7960, 7961, 7962, 7990, 7991, 7992, AquaBI200, AquaBI220) (manufactured by Baxenden); and the Duranate series (e.g., 17B-60P, TPA-B80E, MF-B60B, MF-K60B, SBB-70P, SBN-70D, SBF-70E, E402-B80B, WM44-L70G) (manufactured by Asahi Kasei Corporation).

[0086] Polyisocyanates may be used individually or in combination of two or more types.

[0087] When the surface lubrication layer further contains other components in addition to the hydrophilic polymer and polyurethane, the mixing ratio of the other components is, for example, preferably 5 to 80 parts by mass, more preferably 20 to 60 parts by mass, of the other components per 100 parts by mass of the hydrophilic polymer. With such a mixing ratio, lubrication retention can be further improved. In addition, the film strength of the surface lubrication layer can be further increased.

[0088] Furthermore, if the surface lubrication layer further contains other components in addition to the hydrophilic polymer and polyurethane, it is preferable that the surface lubrication layer is substantially composed of the hydrophilic polymer, polyurethane and other components (particularly polyisocyanate). That is, in one embodiment of the present invention, the surface lubrication layer is substantially composed of the hydrophilic polymer, polyurethane and other components. In a preferred embodiment of the present invention, the surface lubrication layer is substantially composed of the hydrophilic polymer, polyurethane and polyisocyanate. Here, "the surface lubrication layer is substantially composed of the hydrophilic polymer, polyurethane and other components (or polyisocyanate)" means that the total content (in terms of solids) of the hydrophilic polymer, polyurethane and other components (or polyisocyanate) in the surface lubrication layer is greater than 95% by mass (upper limit: 100% by mass).

[0089] Furthermore, in one embodiment of the present invention, the surface lubrication layer is composed of a hydrophilic polymer, polyurethane, and other components (total content of hydrophilic polymer, polyurethane, and other components in the surface lubrication layer (in terms of solid content) = 100% by mass). In a preferred embodiment of the present invention, the surface lubrication layer is composed of a hydrophilic polymer, polyurethane, and polyisocyanate (total content of hydrophilic polymer, polyurethane, and polyisocyanate in the surface lubrication layer (in terms of solid content) = 100% by mass).

[0090] Alternatively, if the medical device is intended for insertion into a body cavity or lumen, such as a catheter, other components may include drugs (bioactive substances) such as anticancer agents, immunosuppressants, antibiotics, antirheumatic drugs, antithrombotic drugs, HMG-CoA reductase inhibitors, ACE inhibitors, calcium channel blockers, antihyperlipidemic drugs, integrin inhibitors, antiallergic agents, antioxidants, GPIIb / IIIa antagonists, retinoids, flavonoids, carotenoids, lipid-improving agents, DNA synthesis inhibitors, tyrosine kinase inhibitors, antiplatelet agents, vascular smooth muscle proliferation inhibitors, anti-inflammatory drugs, bio-derived materials, interferon, and NO production-promoting substances. In this case, there are no particular restrictions on the amount of other components added, and the amounts normally used should be applied in the same manner. The amount of other components added should be appropriately selected considering the severity of the disease being treated, the patient's weight, etc., and ultimately decided by the attending physician.

[0091] The medical devices described above can exhibit excellent lubrication retention (sliding durability), flexibility (especially tip flexibility), and lubrication even under harsh conditions. Therefore, these medical devices can be applied to complex lesion sites.

[0092] [Manufacturing methods for medical devices] The method for manufacturing a medical device according to the present invention is not particularly limited except for forming a surface lubricating layer using the hydrophilic polymer and polyurethane described above, and other components if necessary, and known methods can be applied in the same manner or with appropriate modifications. For example, a preferred method is to prepare a coating solution by adding and mixing the hydrophilic polymer and polyurethane, and other components if necessary, with a solvent, and then coat the substrate layer of the medical device with this coating solution to form a surface lubricating layer.

[0093] Further, as described above, the present invention is characterized by the use of polyurethane having specific properties. Such polyurethane can be obtained by synthesizing (preparing) the polyurethane to have desired properties using a known technique, or by measuring the properties (elongation percentage, Young's modulus, etc.) of a commercially available polyurethane and selecting a polyurethane having the desired properties. That is, the present invention relates to a polyurethane having an elongation percentage of 700% or more and a Young's modulus of 5.0 N / mm 2 or more; preparing a coating liquid containing the polyurethane and a polymer having a carboxyl group or a salt or ester thereof, and applying the coating liquid to a base material layer to form a surface lubricating layer on the base material layer. A method for producing a medical device is provided.

[0094] Further, as described above, the surface lubricating layer may be substantially composed of a hydrophilic polymer and polyurethane. That is, the present invention relates to a polymer having a carboxyl group or a salt or ester thereof, and a polyurethane having an elongation percentage of 700% or more and a Young's modulus of 5.0 N / mm 2 or more, and a solvent alone are mixed to prepare a coating liquid, and the coating liquid is applied to a base material layer to form a surface lubricating layer on the base material layer. A method for producing a medical device is also provided. Further, the present invention relates to a polyurethane having an elongation percentage of 700% or more and a Young's modulus of 5.0 N / mm 2 or more is prepared or selected, and the polyurethane, a polymer having a carboxyl group or a salt or ester thereof, and a solvent alone are mixed to prepare a coating liquid, and the coating liquid is applied to a base material layer to form a surface lubricating layer on the base material layer. A method for producing a medical device is also provided.

[0095] Alternatively, as described above, the surface lubricating layer may be substantially composed of a hydrophilic polymer, polyurethane and polyisocyanate. That is, the present invention relates to a polymer having a carboxyl group or a salt or ester thereof, and a polyurethane having an elongation percentage of 700% or more and a Young's modulus of 5.0 N / mm 2The present invention also provides a method for manufacturing a medical device, comprising preparing a coating solution by mixing only polyurethane, polyisocyanate, and a solvent as described above, and applying the coating solution to a substrate layer to form a surface lubricating layer on the substrate layer. Furthermore, the present invention provides a material with an elongation rate of 700% or more and a Young's modulus of 5.0 N / mm². 2 The present invention also provides a method for manufacturing a medical device, comprising preparing or selecting a polyurethane as described above, mixing only the polyurethane, a polymer having a carboxyl group or its salt or ester, a polyisocyanate, and a solvent to prepare a coating solution, and applying the coating solution to a substrate layer to form a surface lubricating layer on the substrate layer.

[0096] (Preparation or selection process for polyurethane) Here, polyurethane is used with an elongation rate of over 700% and a load capacity of 5.0 N / mm². 2 The material is synthesized (prepared) to have the above Young's modulus. Polyurethane having the above specific properties can be produced by using known techniques or by appropriately modifying known techniques.

[0097] Alternatively, purchase commercially available polyurethane and measure its properties (elongation, Young's modulus, etc.). If the elongation is 700% or more and the Young's modulus is 5.0 N / mm², then it is suitable. 2 You may choose polyurethane, which meets the above criteria.

[0098] (Application process of surface lubrication layer) Here, a coating solution is prepared by dissolving or dispersing a hydrophilic polymer and polyurethane (the polyurethane prepared or selected above) and, if necessary, other components (e.g., polyisocyanate) in a solvent, and this coating solution is applied onto a substrate layer. The solvent that can be used to prepare the coating solution is not particularly limited as long as it can dissolve / disperse the desired components. Specifically, examples include, but are not limited to, water, methanol, ethanol, isopropanol, ethylene glycol and other alcohols, acetone, methyl ethyl ketone, cyclohexanone and other ketones, ethyl acetate and other esters, chloroform and other halides, hexane and other alkanes, tetrahydrofuran (THF) and butyl ether and other ethers, benzene and toluene and other aromatics, amides such as N,N-dimethylformamide (DMF) and sulfoxides such as dimethyl sulfoxide. These may be used individually or in combination of two or more. Here, the hydrophilic polymer and polyurethane may be added together to the solvent, added sequentially (hydrophilic polymer followed by polyurethane or polyurethane followed by hydrophilic polymer) to the same solvent, or dissolved or dispersed in separate solvents before mixing. When using separate solvents for the hydrophilic polymer and polyurethane, the solvents may be the same or different, but for ease of operation, it is preferable that they be the same or allow for uniform dissolution.

[0099] Furthermore, when preparing a coating solution using a hydrophilic polymer, polyurethane, and other components (e.g., polyisocyanate), the hydrophilic polymer, polyurethane, and other components may be added to the solvent together, added in any order (e.g., hydrophilic polymer and polyurethane followed by other components; hydrophilic polymer, polyurethane, and other components in that order), or dissolved or dispersed in a separate solvent before being mixed. When using a separate solvent for the hydrophilic polymer, polyurethane, and other components, the solvent may be the same or different, but for ease of operation, it is preferable that the solvent be the same or one that allows for uniform dissolution.

[0100] After adding the hydrophilic polymer and polyurethane, as well as other components (e.g., polyisocyanate) if necessary, to the solvent, stirring may be performed if necessary to promote dissolution or dispersion.

[0101] The concentrations of the hydrophilic polymer and polyurethane, and other components (e.g., polyisocyanate) in the coating solution are such that the total solid content concentration of the coating solution is preferably 0.1 to 50% by mass, more preferably 0.5 to 10% by mass. Within this range, the coating solution exhibits excellent applicability and production efficiency. The mixing ratio of the hydrophilic polymer and polyurethane, and other components (if necessary) in the coating solution is preferably the same as that described in the section on the surface lubrication layer.

[0102] The amount of coating liquid applied is not particularly limited, but it is preferable that it be an amount that results in the thickness of the surface lubrication layer described above.

[0103] Before applying the coating solution, the substrate layer surface may be pre-treated by UV irradiation, plasma treatment, corona discharge treatment, flame treatment, oxidation treatment, silane coupling treatment, phosphoric acid coupling treatment, surfactant treatment, etc. If the solvent of the coating solution is water only, it is difficult to apply it to a hydrophobic substrate layer surface. However, by treating the substrate layer surface with plasma or surfactant, the substrate layer surface becomes hydrophilic. This improves the wettability of the coating solution to the substrate layer surface, allowing for the formation of a uniform surface lubrication layer.

[0104] The method for applying the coating liquid to the surface of the substrate layer is not particularly limited, and conventionally known methods such as coating / printing, immersion (dipping method, dip coating method), spraying (spray method), spin coating, mixed solution impregnation sponge coating method, bar coating method (e.g., coating method using a wire bar), die coating method, reverse coating method, comma coating method, gravure coating method, and doctor knife method can be applied.

[0105] Furthermore, when forming a surface lubricating layer on the narrow inner surface of catheters, injection needles, etc., the base material layer may be immersed in the coating solution and the system may be degassed by reducing the pressure. By reducing the pressure and degassing, the solution can be quickly penetrated into the narrow inner surface, promoting the formation of the surface lubricating layer.

[0106] Furthermore, when forming a surface lubrication layer on only a portion of the base layer, the surface lubrication layer can be formed on the desired surface portion of the base layer by immersing only a portion of the base layer in the coating liquid and coating that portion of the base layer with the coating liquid.

[0107] If it is difficult to immerse only a portion of the base layer in the coating solution, the surface portion of the base layer that does not require the formation of a surface lubrication layer can be protected (covered, etc.) beforehand with a suitable removable member or material, then the base layer can be immersed in the coating solution to coat the base layer with the coating solution, the protective member (material) on the surface portion of the base layer that does not require the formation of a surface lubrication layer can be removed, and then the surface lubrication layer can be formed on the desired surface portion of the base layer by reacting it through heat treatment or the like. However, the present invention is not limited in any way to these formation methods, and the surface lubrication layer can be formed by using conventionally known methods as appropriate. For example, if it is difficult to immerse only a portion of the base layer in the coating solution, other coating methods may be applied instead of the immersion method (for example, a method of applying the coating solution to a predetermined surface portion of a medical device using an application device such as a spray device, bar coater, die coater, reverse coater, comma coater, gravure coater, spray coater, or doctor's knife). Furthermore, in cases where the structure of a medical device requires both the outer and inner surfaces of a cylindrical device to have a surface lubrication layer, the dipping method is preferred because it allows both the outer and inner surfaces to be coated at once.

[0108] (Drying process for the surface lubricant layer) As described above, it is preferable to dry (heat treat) the coating film after applying the coating liquid to the substrate layer. The drying conditions are not particularly limited as long as the solvent can be removed from the coating film, and drying may be performed using a suitable drying method (apparatus), hot air treatment using a dryer, or natural drying. Furthermore, there are no restrictions on the pressure conditions during drying, and it can be done under normal pressure (atmospheric pressure), or under pressurized or reduced pressure. As drying methods (apparatus), for example, an oven (drying furnace) or a vacuum dryer can be used, but in the case of natural drying, no special drying method (apparatus) is necessary.

[0109] The drying temperature and drying time are not particularly limited and are appropriately selected according to the type of solvent and the heat resistance temperature of the substrate. The drying temperature is preferably 40 to 200°C, more preferably 70 to 150°C. The drying time is preferably 5 minutes to 24 hours, more preferably 20 minutes to 5 hours.

[0110] The drying process may be performed only once, or it may be performed multiple times with different drying conditions.

[0111] As a result, a surface lubricating layer is formed on the substrate layer. After the drying process, the coating formed on the substrate layer may be washed.

[0112] Medical devices produced using this method exhibit excellent lubrication retention (sliding durability), flexibility (especially at the tip), and lubricity, even under harsh conditions. Therefore, these medical devices can be applied to complex lesion sites.

[0113] [Uses of medical devices] The medical devices according to the present invention are used in contact with bodily fluids such as body fluids and blood, and their surfaces are lubricated in aqueous liquids such as bodily fluids and physiological saline, thereby improving operability and reducing damage to tissue mucosa. Specifically, examples include catheters, stents, and guidewires used inside blood vessels. That is, a medical device according to one embodiment of the present invention is a catheter or a guidewire. Other medical devices are also shown below.

[0114] (a) Catheters that are inserted or left in the digestive tract orally or nasally, such as gastric tubes, feeding catheters, and enteral feeding tubes; (b) Catheters that are inserted orally or nasally into the airway or trachea, such as oxygen catheters, oxygen cannulas, endotracheal tubes and cuffs, tracheostomy tubes and cuffs, and endotracheal suction catheters; (c) Catheters such as urethral catheters, urinary catheters, and urethral balloon catheters that are inserted into or left in the urethra or ureter; (d) Catheters to be inserted or indwelled in various body cavities, organs and tissues, such as suction catheters, drainage catheters, and rectal catheters; (e) Catheters to be inserted or indwelled into blood vessels, such as indwelling needles, IVH catheters, thermodilution catheters, angiographic catheters, vascular dilatation catheters and dilators or introducers, or guide wires, stylets and the like for these catheters; (f) Artificial tracheas, artificial bronchi and the like; (g) Medical devices for extracorporeal circulation treatment (artificial lungs, artificial hearts, artificial kidneys, etc.) and circuits therefor.

[0115] Although the embodiments of the present invention have been described in detail, the foregoing description is illustrative and exemplary and not restrictive, and it is clear that the scope of the present invention should be construed by the appended claims.

[0116] The present invention includes the following aspects and modes.

[0117] 1. A medical device comprising: a base material layer, and a surface lubricating layer formed on at least a part of the base material layer, wherein the surface lubricating layer contains a polymer having a carboxyl group or a salt or ester thereof, and polyurethane, wherein the polyurethane has an elongation of 700% or more and a Young's modulus of 5.0 N / mm 2 or more, the medical device.

[0118] 2. The medical device according to 1. above, wherein the polyurethane is contained in the surface lubricating layer in a proportion of 50 to 1200 parts by mass relative to 100 parts by mass of the polymer.

[0119] 3. The medical device according to 1. or 2. above, wherein the polyurethane is contained in the surface lubricating layer in a proportion of 100 to 1000 parts by mass relative to 100 parts by mass of the polymer.

[0120] 4. The medical device according to any one of items 1 to 3 above, wherein the polymer is at least one selected from the group consisting of hyaluronic acid or its alkali metal salt or group 2 metal salt, polyacrylic acid or its alkali metal salt or group 2 metal salt, and a polymer having a structural unit represented by the following formula (1).

[0121] [ka]

[0122] In the formula, X 1 and X 2 Each of these is independently a hydrogen atom, an alkali metal, a Group 2 metal, or a linear or branched alkyl group having 1 to 24 carbon atoms. base It represents.

[0123] 5. The medical device according to any one of items 1 to 4 above, wherein the surface lubricating layer further comprises a polyisocyanate or a crosslinked product thereof.

[0124] 6. The medical device is a catheter or a guidewire, as described in any of items 1 to 5 above.

[0125] 7. The elongation rate is 700% or more, and the Young's modulus is 5.0 N / mm². 2 Prepare or select polyurethane that meets the above criteria; A coating solution is prepared containing the aforementioned polyurethane, a polymer having a carboxyl group or a salt or ester thereof, A method for manufacturing a medical device, comprising applying the coating liquid to a substrate layer to form a surface lubricating layer on the substrate layer. [Examples]

[0126] The effects of the present invention will be explained using the following examples and comparative examples. However, the technical scope of the present invention is not limited to the following examples. In the following examples, unless otherwise specified, the operations were carried out at room temperature (25°C). Unless otherwise specified, "%" and "parts" mean "mass%" and "parts by mass," respectively.

[0127] Example 1 0.1 g of sodium polyacrylate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., degree of polymerization: 30,000-40,000) was added to 60 g of water and stirred for 2 hours to prepare an aqueous solution of sodium polyacrylate. To this aqueous solution of sodium polyacrylate, a non-yellowing isocyanate ester polyurethane aqueous dispersion (polyurethane concentration: 50% by mass) (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., Superflex® E-2000, elongation: 1350%, Young's modulus: 11 N / mm²) was added. 2 100% Modulus: 0.7 N / mm 2 Polyacrylate (also referred to as "polyurethane E2000" or "E2000"), with an EO content of over 20 mol%, a weight-average molecular weight of 100,000 or more, and an average particle size in the aqueous dispersion of 700 nm or less, was mixed so that the mass ratio (solid content ratio) of sodium polyacrylate / E2000 was 100 / 400, and the mixture was stirred for 10 minutes to obtain a coating solution in which the total solid content concentration of the resin components (sodium polyacrylate and E2000) was 0.8% by mass.

[0128] Next, the coating solution obtained above was applied to a polyethylene terephthalate (PET) film (manufactured by Toyobo Co., Ltd., CosmoShine® A4100, thickness: 100 μm) using a wire bar under conditions of 25°C and 45% RH relative humidity, so that the film thickness (dry film thickness) was 2-3 μm, forming a coating on the PET film. Subsequently, the film with the coating was dried in a drying oven at 80°C for 30 minutes, and then at 100°C for 30 minutes, thereby forming a lubricating layer (dry film thickness: 2-3 μm) containing sodium polyacrylate and E2000 on the PET film (Sample 1).

[0129] Example 2 In Example 1, instead of polyurethane E2000, a non-yellowing isocyanate ester / ether-based polyurethane (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., Superflex® 300, elongation: 1500%, Young's modulus: 5.4 N / mm²) was used. 2 100% Modulus: 1.7 N / mm 2 A lubricating layer (dry film thickness: 2-3 μm) containing sodium polyacrylate and SF300 was formed on a PET film in the same manner as in Example 1, except that an EO content of over 20 mol%, weight-average molecular weight of 100,000 or more, and average particle size in aqueous dispersion of 70 nm or less (also referred to as "polyurethane SF300" or "SF300") was used (Sample 2).

[0130] Example 3 0.05 g of sodium hyaluronate (manufactured by Tokyo Chemical Industry Co., Ltd., product code: H0603, derived from chicken comb, molecular weight: 350,000 or more (on a dry basis)) was added to 40 g of water and stirred for 2 hours to prepare an aqueous solution of sodium hyaluronate. Polyurethane SF300 was mixed into this aqueous solution of sodium hyaluronate so that the mass ratio (solid content ratio) of sodium hyaluronate / SF300 was 100 / 400, and the mixture was stirred for 10 minutes to obtain a coating solution in which the total solid content concentration of the resin components (sodium hyaluronate and SF300) was 0.6% by mass.

[0131] Next, the coating solution obtained above was applied to a PET film (Toyobo Co., Ltd., CosmoShine® A4100, thickness: 100 μm) using a wire bar under conditions of 25°C and 45% RH relative humidity, so that the film thickness (dry film thickness) was 2-3 μm, forming a coating on the PET film. Subsequently, the film with the coating was dried in a drying oven at 80°C for 30 minutes, and then at 100°C for 30 minutes, thereby forming a lubricating layer (dry film thickness: 2-3 μm) containing sodium hyaluronate and SF300 on the PET film (Sample 3).

[0132] Example 4 Half-ethyl ester (degree of esterification: 40-50%) of methyl vinyl ether maleic anhydride copolymer (ISP, GANTREZ AN-169) was added to acetone to a concentration of 2.6% by mass and stirred for 1 hour to dissolve. Next, the resulting solution was mixed with an aqueous sodium bicarbonate solution in an amount of sodium bicarbonate equal to 1.05 mol equivalents relative to the unit unit of the half-ethyl ester of methyl vinyl ether maleic anhydride copolymer, and stirred for 1 hour. As a result, all carboxylic acid groups in the half-ethyl ester of methyl vinyl ether maleic anhydride copolymer were neutralized by sodium carboxylate (the hydrophilic polymer is composed of the following constituent units). The hydrophilic polymer obtained here will be referred to as "Hydrophilic Polymer 1" below.

[0133] [ka]

[0134] The hydrophilic polymer 1 and polyurethane E2000 obtained above were mixed so that the mass ratio (solid content ratio) of hydrophilic polymer 1 / E2000 was 100 / 400. This mixture was adjusted so that the total solid content concentration of the resin components (hydrophilic polymer 1 and E2000) was 6.0% by mass and the mixing ratio (mass ratio) of acetone to water was 50 / 50, and the mixture was stirred for 1 hour to obtain a coating solution.

[0135] Next, the coating solution obtained above was applied to a PET film (Toyobo Co., Ltd., CosmoShine® A4100, thickness: 100 μm) using a wire bar under conditions of 25°C and 45% RH relative humidity, so that the film thickness (dry film thickness) was 2-3 μm, forming a coating on the PET film. Subsequently, the film with the coating was dried in a drying oven at 80°C for 30 minutes, and then at 100°C for 30 minutes, thereby forming a lubricating layer (dry film thickness: 2-3 μm) containing hydrophilic polymer 1 and E2000 on the PET film (Sample 4).

[0136] Comparative Example 1 Sodium polyacrylate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., degree of polymerization: 30,000-40,000) was added to water to a solid content concentration of 0.2% by mass, and the mixture was stirred for 2 hours to dissolve it. Next, to prevent repelling during application, a nonionic surfactant (Neugen® EA87, polyoxyethylene styrylphenyl ether, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) was added at a ratio of 5% by mass relative to the sodium polyacrylate to obtain a coating solution.

[0137] Next, the coating solution obtained above was applied to a PET film (Toyobo Co., Ltd., CosmoShine® A4100, thickness: 100 μm) using a wire bar under conditions of 25°C and 45% RH relative humidity, so that the film thickness (dry film thickness) was 2-3 μm, forming a coating on the PET film. Subsequently, the film with the coating was dried in a drying oven at 80°C for 30 minutes, and then at 100°C for 30 minutes, thereby forming a lubricating layer containing sodium polyacrylate (dry film thickness: 2-3 μm) on the PET film (Comparative Sample 1).

[0138] Comparative Example 2 Polyacrylamide (manufactured by Tokyo Chemical Industry Co., Ltd., Mw = 400,000 to 800,000) and polyurethane E2000 were mixed so that the mass ratio (solids content ratio) of polyacrylamide to E2000 was 100 / 400. This mixture was added to water so that the total solids content concentration of the resin components (polyacrylamide and E2000) was 8.6% by mass, and the mixture was stirred for 2 hours to obtain a coating solution.

[0139] Next, the coating solution obtained above was applied to a PET film (Toyobo Co., Ltd., CosmoShine® A4100, thickness: 100 μm) using a wire bar under conditions of 25°C and 45% RH relative humidity, to form a coating film on the PET film with a film thickness (dry film thickness) of 2-3 μm. Subsequently, the film with the coating film was dried in a drying oven at 80°C for 30 minutes, and then at 100°C for 30 minutes, thereby forming a lubricating layer (dry film thickness: 2-3 μm) containing polyacrylamide and E2000 on the PET film (comparative sample 2).

[0140] Comparative Example 3 In Comparative Example 2, a lubricating layer (dry film thickness: 2-3 μm) containing polyacrylamide and SF300 was formed on a PET film in the same manner as in Comparative Example 2, except that polyurethane SF300 was used instead of polyurethane E2000 (Comparative Sample 3).

[0141] Comparative Example 4 Polyvinylpyrrolidone (manufactured by Tokyo Chemical Industry Co., Ltd., K90, weight-average molecular weight = 360,000) and polyurethane E2000 were mixed so that the mass ratio (solid content ratio) of polyvinylpyrrolidone / E2000 was 100 / 400. This mixture was added to water so that the total solid content concentration of the resin components (polyvinylpyrrolidone and E2000) was 10% by mass, and the mixture was stirred for 2 hours to obtain a coating solution.

[0142] Next, the coating solution obtained above was applied to a PET film (Toyobo Co., Ltd., CosmoShine® A4100, thickness: 100 μm) using a wire bar under conditions of 25°C and 45% RH relative humidity, so that the film thickness (dry film thickness) was 2-3 μm, forming a coating on the PET film. Subsequently, the film with the coating was dried in a drying oven at 80°C for 30 minutes, and then at 100°C for 30 minutes, thereby forming a lubricating layer (dry film thickness: 2-3 μm) containing polyvinylpyrrolidone and E2000 on the PET film (comparative sample 4).

[0143] Comparative Example 5 In Comparative Example 4, a lubricating layer (dry film thickness: 2-3 μm) containing polyvinylpyrrolidone and SF300 was formed on a PET film in the same manner as in Comparative Example 4, except that polyurethane SF300 was used instead of polyurethane E2000 (Comparative Sample 5).

[0144] [Sliding durability evaluation 1] For samples 1 to 4 of Examples 1 to 4 and comparative samples 1 to 5 of Comparative Examples 1 to 5, the sliding durability of the lubricating layer was evaluated using the friction measuring instrument (Handy Tribomaster TL201, manufactured by Trinity Labs) 10 shown in Figure 1, according to the method described below.

[0145] Specifically, each sample 3 was fixed in a petri dish 2 with the lubricated surface facing upwards, and immersed in water 1 to a height sufficient to completely submerge the sample 3. This petri dish 2 was placed on the movable table 6 of the friction measuring machine 10 shown in Figure 1. A hydrogenated styrene thermoplastic elastomer (SEBS) terminal (φ10 mm) 4 was brought into contact with the sample 3, and a load 5 of 100 g was applied to the terminal. With a sliding distance of 15 mm and a sliding speed of 16.7 mm / sec, the movable table 6 was moved back and forth horizontally 10 times, and the sliding resistance value (gf) was measured for the 1st, 5th, and 10th reciprocations. The results are shown in Table 1 below. In Table 1 below, a sliding resistance value of less than 1.0 gf for the 10th reciprocation is indicated as "◎", a sliding resistance value of 1.0 gf or more and less than 5.0 gf for the 10th reciprocation is indicated as "〇", and a sliding resistance value of 5.0 gf or more for the 10th reciprocation is indicated as "×".

[0146] [Table 1]

[0147] The results in Table 1 show that using polymers containing carboxyl groups, etc., as hydrophilic polymers can significantly improve sliding durability.

[0148] Example 5 Hydrophilic polymer 1 was obtained in the same manner as in Example 4.

[0149] This hydrophilic polymer 1 and non-yellowing isocyanate ester polyurethane (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., Superflex® 500M, elongation: 1100%, Young's modulus: 319 N / mm²) 2 100% Modulus: 6.2 N / mm 2Polyurethane SF500M (also referred to as "Polyurethane SF500M" or "500M"), with an EO content of over 20 mol%, a weight-average molecular weight of 100,000 or more, and an average particle size in the aqueous dispersion of 140 nm, was mixed so that the mass ratio (solid content ratio) of the hydrophilic polymer 1 / 500M was 100 / 400. This mixture was adjusted so that the total solid content concentration of the resin components (hydrophilic polymer 1 and 500M) was 6.0% by mass and the mixing ratio (mass ratio) of acetone to water was 50 / 50, and the mixture was stirred for 1 hour to obtain a coating solution.

[0150] A Ni-Ti wire (outer diameter = 0.34 mm) was coated with a thermoplastic polyurethane resin to a thickness of approximately 35 μm to obtain a coated wire 1 (outer diameter = 0.41 mm) with a polyurethane resin coating (polyurethane base layer) (thickness: approximately 35 μm) on the wire. Next, this coated wire 1 was immersed for 5 seconds in a polyvinyl chloride (PVC) tetrahydrofuran (THF) solution (PVC concentration = 10 mass%) at 25°C and 45% RH relative humidity, then pulled out at a speed of 50 mm / sec and air-dried for 10 minutes to form a PVC coating (PVC intermediate layer) (thickness: approximately 4 μm) on the surface of coated wire 1 (base wire 1).

[0151] The base wire 1 was immersed in the coating solution prepared above for 5 seconds, then pulled out at a speed of 50 mm / sec, and dried in a drying oven maintained at 120°C for 2 hours to form a lubricating layer (dry film thickness: 4 μm) on the PVC intermediate layer. This resulted in a wire with a lubricating layer containing hydrophilic polymer 1 and 500M formed on the PVC intermediate layer (Sample 5).

[0152] Example 6 In Example 5, a lubricating layer (dry film thickness: 4 μm) was formed on the PVC intermediate layer in the same manner as in Example 5, except that polyurethane SF300 was used instead of polyurethane 500M. As a result, hydrophilic polymer 1 and SF300 A wire was obtained in which a lubricating layer containing the material was formed (Sample 6).

[0153] Example 7 In Example 5, a lubricating layer (dry film thickness: 4 μm) was formed on the PVC intermediate layer in the same manner as in Example 5, except that polyurethane E2000 was used instead of polyurethane 500M. As a result, hydrophilic polymer 1 and E2000 A wire was obtained in which a lubricating layer containing the material was formed (Sample 7).

[0154] Comparative Example 6 In Example 5, instead of polyurethane 500M, a non-yellowing isocyanate ester / ether-based polyurethane (Superflex® 150, manufactured by Daiichi Kogyo Seiyaku Co., Ltd., elongation: 330%, Young's modulus: 807 N / mm²) was used. 2 100% Modulus: 19.0 N / mm 2 Except for using a polymer with an EO content of less than 15 mol% (hereinafter also referred to as "polyurethane SF150" or "SF150"), a lubricating layer (dry film thickness: 4 μm) was formed on the PVC intermediate layer in the same manner as in Example 5. This resulted in a wire having a lubricating layer containing hydrophilic polymer 1 and SF150 formed on the PVC intermediate layer (comparative sample 6).

[0155] Comparative Example 7 In Example 5, instead of polyurethane 500M, a non-yellowing isocyanate ester polyurethane (Superflex® 210, manufactured by Daiichi Kogyo Seiyaku Co., Ltd., elongation: 5%, Young's modulus: 1396 N / mm²) was used. 2 Except for using a 100% modulus polymer (hereinafter also referred to as "polyurethane SF210" or "SF210"), a lubricating layer (dry film thickness: 4 μm) was formed on the PVC intermediate layer in the same manner as in Example 5. This resulted in a wire having a lubricating layer containing hydrophilic polymer 1 and SF210 formed on the PVC intermediate layer (comparative sample 7).

[0156] Comparative Example 8 In Example 5, instead of polyurethane 500M, a non-yellowing isocyanate ester polyurethane (Superflex® 740, manufactured by Daiichi Kogyo Seiyaku Co., Ltd., elongation: 1300%, Young's modulus: 0.3 N / mm²) was used.2 100% Modulus: 1.0 N / mm 2 Except for using "Polyurethane SF740" or "SF740" (hereinafter referred to as "Polyurethane SF740"), a lubricating layer (dry film thickness: 4 μm) was formed on the PVC intermediate layer in the same manner as in Example 5. This resulted in a wire having a lubricating layer containing hydrophilic polymer 1 and SF740 formed on the PVC intermediate layer (Comparative Sample 8).

[0157] Comparative Example 9 In Example 5, instead of polyurethane 500M, a non-yellowing isocyanate carbonate-based polyurethane (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., Superflex® registered trademark) was used. 470, Elongation: 640%, Young's modulus: 13 N / mm 2 100% Modulus: 2.5 N / mm 2 Except for using a polymer with a weight-average molecular weight of 100,000 or more and an average particle size of 50 nm or less in an aqueous dispersion (also referred to as "polyurethane SF470" or "SF470"), a lubricating layer (dry film thickness: 4 μm) was formed on the PVC intermediate layer in the same manner as in Example 5. This resulted in a wire having a lubricating layer containing hydrophilic polymer 1 and SF740 formed on the PVC intermediate layer (comparative sample 9).

[0158] [Sliding durability evaluation 2] For samples 5-7 of Examples 5-7 and comparative samples 6-9 of Comparative Examples 6-9, the sliding durability of the lubricating layer was evaluated using the friction measuring instrument (Handy Tribomaster TL201, manufactured by Trinity Labs) 10 shown in Figure 1, according to the method described below.

[0159] Specifically, each sample 3 was fixed in a petri dish 2 with the lubricated surface facing upwards, and immersed in water 1 to a height sufficient to completely submerge the sample 3. This petri dish 2 was placed on the movable table 6 of the friction measuring machine 10 shown in Figure 1. A hydrogenated styrene-based thermoplastic elastomer (SEBS) terminal (φ10 mm) 4 was brought into contact with the sample 3, and a load 5 of 100 g was applied to the terminal. With a sliding distance of 15 mm and a sliding speed of 16.7 mm / sec, the movable table 6 was moved back and forth horizontally 100 times, and the sliding resistance value (gf) was measured for the 1st, 5th, 10th, 30th, 50th, and 100th reciprocations. The results are shown in Table 2 below. In Table 2 below, a "◎" indicates that the resistance increase from the 1st to the 100th cycle (= (sliding resistance value at the 100th cycle) - (sliding resistance value at the 1st cycle)) is less than 1gf and the resistance value at the 100th cycle is less than 2.5gf; a "〇" indicates that the resistance increase from the 1st to the 50th cycle (= (sliding resistance value at the 50th cycle) - (sliding resistance value at the 1st cycle)) is less than 1gf, the resistance value at the 50th cycle is less than 2.5gf, and the resistance value at the 100th cycle is 2.5gf or more; a "△" indicates that the resistance increase from the 1st to the 10th cycle (= (sliding resistance value at the 10th cycle) - (sliding resistance value at the 1st cycle)) is less than 1gf, the resistance value at the 10th cycle is less than 2.5gf, and the resistance value at the 50th cycle is 2.5gf or more; and a "×" indicates that the sliding resistance value at the 10th cycle is 2.5gf or more.

[0160] [Table 2]

[0161] From the results in Table 2, the elongation rate is 700% or more and the Young's modulus is 5.0 N / mm². 2 As described above, it can be seen that by using polyurethane, the surface lubrication layer can exhibit excellent sliding durability. On the other hand, Comparative Examples 6, 7, and 9, whose elongation rate falls outside the range of the present invention, and Comparative Example 8, whose Young's modulus falls outside the range of the present invention, exhibit inferior sliding durability.

[0162] In particular, samples 6 and 7 of Examples 6 and 7 showed excellent lubrication retention (sliding durability), with sliding resistance values ​​of less than 2.0 gf from the 1st to the 100th cycle. This is presumed to be because the polyurethane used in samples 6 and 7 has a high elongation rate and a low 100% modulus, allowing it to follow well due to the swelling of the hydrophilic polymer, and because of its high Young's modulus, it can better maintain the film strength of the surface lubrication layer against sliding. Furthermore, while comparative sample 9 of comparative example 9 had a sliding resistance value of 2.5gf or more on the 10th cycle, the increase in resistance value from the 1st to the 10th cycle (=(sliding resistance value on the 10th cycle) - (sliding resistance value on the 1st cycle)) was less than 1gf, and the resistance value on the 10th cycle was less than 4gf. Compared to the other comparative samples 6 to 8 [resistance increase (=(sliding resistance value on the 10th cycle) - (sliding resistance value on the 1st cycle)) = more than 5gf, resistance value on the 10th cycle = more than 10gf], it demonstrated superior sliding durability of the surface lubrication layer and a lower sliding resistance value.

[0163] Example 8 In Example 7, a lubricating layer (dry film thickness: 4 μm) was formed on the PVC intermediate layer in the same manner as in Example 7, except that hydrophilic polymer 1 and polyurethane E2000 were mixed so that the mass ratio (solid content ratio) of hydrophilic polymer 1 / E2000 was 100 / 50. As a result, a wire was obtained in which a lubricating layer containing hydrophilic polymer 1 and E2000 in a mixing ratio of 100 / 50 was formed on the PVC intermediate layer (Sample 8).

[0164] Example 9 In Example 7, a lubricating layer (dry film thickness: 4 μm) was formed on the PVC intermediate layer in the same manner as in Example 7, except that hydrophilic polymer 1 and polyurethane E2000 were mixed so that the mass ratio (solid content ratio) of hydrophilic polymer 1 / E2000 was 100 / 100. As a result, a wire was obtained in which a lubricating layer containing hydrophilic polymer 1 and E2000 in a 100 / 100 mixing ratio was formed on the PVC intermediate layer (Sample 9).

[0165] Example 10 In Example 7, a lubricating layer (dry film thickness: 4 μm) was formed on the PVC intermediate layer in the same manner as in Example 7, except that hydrophilic polymer 1 and polyurethane E2000 were mixed so that the mass ratio (solid content ratio) of hydrophilic polymer 1 / E2000 was 100 / 200. As a result, a wire was obtained in which a lubricating layer containing hydrophilic polymer 1 and E2000 in a mixing ratio of 100 / 200 was formed on the PVC intermediate layer (Sample 10).

[0166] Example 11 In Example 7, a lubricating layer (dry film thickness: 4 μm) was formed on the PVC intermediate layer in the same manner as in Example 7, except that hydrophilic polymer 1 and polyurethane E2000 were mixed so that the mass ratio (solid content ratio) of hydrophilic polymer 1 / E2000 was 100 / 600. As a result, a wire was obtained in which a lubricating layer containing hydrophilic polymer 1 and E2000 in a mixing ratio of 100 / 600 was formed on the PVC intermediate layer (Sample 11).

[0167] Example 12 In Example 7, a lubricating layer (dry film thickness: 4 μm) was formed on the PVC intermediate layer in the same manner as in Example 7, except that hydrophilic polymer 1 and polyurethane E2000 were mixed so that the mass ratio (solid content ratio) of hydrophilic polymer 1 / E2000 was 100 / 800. As a result, a wire was obtained in which a lubricating layer containing hydrophilic polymer 1 and E2000 in a mixing ratio of 100 / 800 was formed on the PVC intermediate layer (Sample 12).

[0168] Example 13 In Example 7, a lubricating layer (dry film thickness: 4 μm) was formed on the PVC intermediate layer in the same manner as in Example 7, except that hydrophilic polymer 1 and polyurethane E2000 were mixed so that the mass ratio (solid content ratio) of hydrophilic polymer 1 / E2000 was 100 / 1000. As a result, a wire was obtained in which a lubricating layer containing hydrophilic polymer 1 and E2000 in a mixing ratio of 100 / 1000 was formed on the PVC intermediate layer (Sample 13).

[0169] Example 14 In Example 7, a lubricating layer (dry film thickness: 4 μm) was formed on the PVC intermediate layer in the same manner as in Example 7, except that hydrophilic polymer 1 and polyurethane E2000 were mixed so that the mass ratio (solid content ratio) of hydrophilic polymer 1 / E2000 was 100 / 1200. As a result, a wire was obtained in which a lubricating layer containing hydrophilic polymer 1 and E2000 in a mixing ratio of 100 / 1200 was formed on the PVC intermediate layer (Sample 14).

[0170] [Sliding durability evaluation 3] For samples 7 to 14 of the above examples 7 to 14, the sliding durability of the lubricating layer was evaluated according to the method and judgment criteria described in [Sliding Durability Evaluation 2] above. The results are shown in Table 3 below.

[0171] [Table 3]

[0172] Example 15 Hydrophilic polymer 1 was obtained in the same manner as in Example 4.

[0173] The hydrophilic polymer 1 and polyurethane E2000 were mixed so that the mass ratio (solid content ratio) of hydrophilic polymer 1 to E2000 was 100 / 400. This mixture was adjusted so that the total solid content concentration of the resin components (hydrophilic polymer 1 and E2000) was 6.0% by mass and the mixing ratio (mass ratio) of acetone to water was 50 / 50 to prepare the coating solution.

[0174] A coated wire (outer diameter = 0.41 mm) was obtained by coating a Ni-Ti wire (outer diameter = 0.34 mm) with a thermoplastic polyurethane resin to a thickness of approximately 35 μm, forming a polyurethane resin coating (polyurethane underlayer) on the wire.

[0175] Next, the coated wire was immersed in the coating solution prepared above for 5 seconds, then pulled out at a speed of 50 mm / sec, and dried in a drying oven maintained at 120°C for 2 hours to form a lubricating layer (dry film thickness: 4 μm) on the coated wire. This resulted in a wire with a lubricating layer containing hydrophilic polymers 1 and E2000 formed on the polyurethane resin coating (Sample 17).

[0176] [Sliding durability evaluation 4] The sliding durability of the lubricating layer was evaluated for samples 7 and 15 of Examples 7 and 15 according to the method and criteria described in [Sliding Durability Evaluation 2] above. The results are shown in Table 4 below.

[0177] [Table 4]

[0178] Example 16 In Example 5, a coated wire 2 was obtained by forming a polyurethane resin coating (polyurethane underlayer) (thickness: approximately 35 μm) on the wire, except that a Ni-Ti wire with the shape shown in Figure 3 was used instead of the Ni-Ti wire (outer diameter = 0.34 mm) in the same manner as in Example 5. Next, in Example 5, a PVC coating (PVC intermediate layer) (thickness: approximately 4 μm) was formed on the surface of the coated wire 2 (base wire 2), except that the coated wire 2 obtained above was used instead of the coated wire 1 in Example 5. That is, the base wire 2 has a structure in which a polyurethane resin coating (polyurethane underlayer) (thickness: approximately 35 μm) and a PVC coating (PVC intermediate layer) (thickness: approximately 4 μm) are sequentially formed on the wire surface.

[0179] The Ni-Ti wire (total length: 1800 mm) 30 used in this example has the following structure, as shown in Figure 3: the area from the tip 31 to 10 mm (straight tip section 32) is straight with a diameter of 0.085 mm; the area from 10 mm to 260 mm (tapered section 33) is tapered, expanding from a diameter of 0.085 mm to 0.34 mm; and the area from 260 mm onward from the tip is straight with a diameter of 0.34 mm, continuing to the rear end 34. Furthermore, as shown in Figure 5B, the portion from the tip to 10 mm (straight tip section) has been heat-treated to have a shape inclined at approximately 45°.

[0180] The coated wire 2, obtained by coating a Ni-Ti wire with a thermoplastic polyurethane resin to a thickness of approximately 35 μm, has a straight shape with a diameter of 0.155 mm in the region from the tip to 10 mm (straight tip portion), a tapered shape that expands in diameter from 0.155 mm to 0.41 mm in the region from 10 mm to 260 mm (tapered portion), and a structure in which the region from 260 mm onward has a straight shape with a diameter of 0.41 mm that continues to the rear end. Similarly, the base wire 2, obtained by coating the coated wire 2 with PVC to a thickness of approximately 4 μm, has a straight shape with a diameter of 0.163 mm in the region from the tip to 10 mm (straight tip portion), a tapered shape that expands in diameter from 0.163 mm to 0.418 mm in the region from 10 mm to 260 mm (tapered portion), and a structure in which the region from 260 mm onward has a straight shape with a diameter of 0.418 mm that continues to the rear end.

[0181] In Example 7, a lubricating layer (dry film thickness: 4 μm) was formed on the PVC intermediate layer in the same manner as in Example 7, except that base wire 2 was used instead of base wire 1. This resulted in a wire (Sample 16) with a lubricating layer formed on the PVC intermediate layer containing hydrophilic polymer 1 and E2000 in a 100 / 400 mixing ratio.

[0182] Comparative Example 10 A polyurethane resin coating (polyurethane underlayer) (thickness: approximately 35 μm) was formed on a Ni-Ti wire of the shape shown in Figure 3 in the same manner as described in Example 16 (coated wire 2). Next, this coated wire 2 was immersed for 5 seconds in a tetrahydrofuran (THF) solution of polyvinyl chloride (PVC) and 4,4'-diphenylmethane diisocyanate (MDI) (PVC concentration = 5% by mass, MDI concentration = 5% by mass) at 25°C and 45% RH relative humidity, then pulled out at a speed of 50 mm / sec and dried at room temperature (25°C) for 30 minutes to form a coating containing PVC and MDI (PVC / MDI intermediate layer) (thickness: approximately 4 μm) on the surface of coated wire 2 (base wire 3).

[0183] This base wire 3 was immersed for 5 seconds in a 1% by mass THF solution of half-ethyl ester (40-50% esterification degree) of methyl vinyl ether maleic anhydride copolymer (ISP, GANTREZ AN-169), then pulled out at a speed of 50 mm / sec and dried at approximately 60°C for 12 hours (base wire 3'). Next, this base wire 3' was immersed for 30 minutes in warm water at approximately 60°C (pH 8.2) containing 0.1% by mass of NaCl and 0.05% by mass of sodium bicarbonate (NaHCO3), then washed with warm water at approximately 60°C for 1 minute, dried at room temperature (25°C), and a wire was obtained in which a lubricating layer (dry film thickness: approximately 1-2 μm) was formed on the PVC / MDI intermediate layer (comparative sample 10).

[0184] Comparative Example 11 In Comparative Example 10, a wire was obtained in the same manner as in Comparative Example 10, except that 4,4'-diphenylmethane diisocyanate (MDI) was not used, and a lubricating layer (dry film thickness: approximately 1-2 μm) was formed on the PVC intermediate layer (Comparative Sample 11).

[0185] [Sliding durability evaluation 5] The sliding durability of the lubricating layer was evaluated for Sample 16 of Example 16 and Comparative Samples 10-11 of Comparative Examples 10-11, according to the method and criteria described in [Sliding Durability Evaluation 2] above. The results are shown in Table 5 below. 5Next, the region from 260 mm from the tip was brought into contact with a hydrogenated styrene-based thermoplastic elastomer (SEBS) terminal (φ10 mm) 4, and the sliding durability in the region from 260 mm from the tip was evaluated.

[0186] [Evaluation of tip abutment resistance] For sample 16 of Example 16 and comparative samples 10-11 of Comparative Examples 10-11, the tip abutment resistance was evaluated using the micro load cell 40 shown in Figure 4, according to the method described below. In Example 16, a lubricating layer (dry film thickness: 4 μm) was formed on the PVC intermediate layer of the base wire 2 in the same manner as in Example 16, except that the coating liquid prepared in Examples 1-15 was used instead. When the tip abutment resistance of the sample was evaluated according to the method and judgment criteria described below, all results were "○".

[0187] Specifically, each sample 43 is fixed 10 mm from the tip using a chuck 44 attached to a load cell 42, and is pressed down vertically at a test speed of 5 mm / sec towards a base 46 to which #1200 grit abrasive paper (anti-slip abrasive paper) (not shown) is attached. The load (L1(gf)) is measured when the tip of the sample touches the abrasive paper and is pressed down 2 mm. Similarly, the load (L0(gf)) is measured for the coated wire 2 when it is pressed down 2 mm. Each measurement was performed three times, and the average value was used.

[0188] For each sample, the difference (=L1(gf)-L0(gf)(absolute value)) between the load (L0(gf)) of coated wire 2 (polyurethane resin coating) and the load (L1(gf)) of each sample (with a laminated PVC intermediate layer and lubricating layer) was calculated. The results are shown in Table 5 below. In Table 5 below, a difference (=L1(gf)-L0(gf)(absolute value)) of less than 0.1gf is indicated by "○", and a difference of 0.1gf or more is indicated by "×". A small difference (=L1(gf)-L0(gf)(absolute value)) indicates flexibility.

[0189] [Table 5]

[0190] [Evaluation of guidewire tip reachability using a vascular model] For sample 16 of Example 16 and comparative samples 10-11 of Comparative Examples 10-11, the guidewire tip reachability was evaluated using the blood vessel model 50 shown in Figure 5A, according to the method described below. Figure 5A is a plan view showing a part of the blood vessel model.

[0191] The blood vessel model 50 had a hollow passage formed inside a transparent resin plate-shaped member. The passage had a straight main tube 51 and side branches 52 branching off from the main tube 51. The inner diameter of the main tube 51 was 3 mm. The inner diameter of the side branches 52 was 2.2 mm. The side branches 52 had six arc-shaped curved sections 53 that curved alternately in opposite directions, and straight sections 54 connecting adjacent curved sections 53. The radius of curvature R of the centerline passing through the center of the lumen of the curved sections 53 was 4.5 mm. All the straight sections 54 were parallel and inclined at an angle θ of 50° with respect to the main tube 51. The length S of the straight sections 54 was 5 mm.

[0192] After filling the blood vessel model with water, each sample is inserted from the main tube 51 into the side branch 52. The sample is then rotated as needed to adjust the direction of the tip to facilitate its advancement, and then pushed forward. Each sample was used with the tip inclined at approximately 45° for the first 10 mm (straight tip portion), as shown in Figure 5B, so that the tip of the sample could be inserted from the main tube 51 into the side branch 52.

[0193] As a result, after insertion into the lateral branch 52, sample 16 was able to easily advance through two or more curved sections 53 at its tip. From the above results, it is considered that the medical device according to the present invention can be easily inserted even into complex lesion sites. The above results are thought to be due to the excellent sliding durability of sample 16 even under extremely harsh conditions, and its excellent flexibility (especially the flexibility of the tip).

[0194] In contrast, after insertion into the lateral branch 52, the tip of comparative sample 10 could not pass the second curved section 53. mosquito Based on the results in Table 5 above, it is thought that the above result is due to the inferior flexibility (especially the flexibility of the tip) of comparative sample 10.

[0195] Furthermore, the comparative sample 11 was unable to advance its tip immediately after being inserted into the lateral branch 52. This is presumed to be because, as shown in Table 3 above, comparative sample 11 has inferior sliding durability (its sliding resistance value increases even under light loads).

[0196] Example 17 A hydrophilic polymer 1 was obtained in the same manner as in Example 1.

[0197] The hydrophilic polymer 1, polyurethane E2000, and reactive aqueous polyisocyanate (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., Elastron® BN-77; hereinafter also referred to as "Elastron BN-77" or "BN-77") obtained above were mixed in a mass ratio (solids ratio) of hydrophilic polymer 1 / E2000 / BN-77 of 100 / 400 / 5. This mixture was adjusted so that the total solids concentration of the resin components (hydrophilic polymer 1, E2000, and BN-77) was 6.2% by mass and the mixing ratio (mass ratio) of acetone to water was 50 / 50, and the mixture was stirred for 1 hour to obtain a coating solution.

[0198] In Example 16, a lubricating layer (dry film thickness: 4 μm) was formed on the PVC intermediate layer in the same manner as in Example 16, except that the coating solution prepared above was used instead. This resulted in a wire (Sample 17) with a lubricating layer formed on the PVC intermediate layer containing hydrophilic polymers 1, E2000, and BN-77 in a mixing ratio of 100 / 400 / 5.

[0199] Example 18 A hydrophilic polymer 1 was obtained in the same manner as in Example 1.

[0200] The hydrophilic polymer 1, polyurethane E2000, and elastron BN-77 obtained above were mixed in a mass ratio (solid content ratio) of hydrophilic polymer 1 / E2000 / BN-77 of 100 / 400 / 20. This mixture was adjusted so that the total solid content concentration of the resin components (hydrophilic polymer 1, E2000, and BN-77) was 6.2% by mass and the mixing ratio (mass ratio) of acetone to water was 50 / 50, and the mixture was stirred for 1 hour to obtain a coating solution.

[0201] In Example 16, a lubricating layer (dry film thickness: 4 μm) was formed on the PVC intermediate layer in the same manner as in Example 16, except that the coating solution prepared above was used instead. This resulted in a wire (Sample 18) with a lubricating layer formed on the PVC intermediate layer containing hydrophilic polymers 1, E2000, and BN-77 in a mixing ratio of 100 / 400 / 20.

[0202] Example 19 A hydrophilic polymer 1 was obtained in the same manner as in Example 1.

[0203] The hydrophilic polymer 1, polyurethane E2000, and elastron BN-77 obtained above were mixed in a mass ratio (solid content ratio) of hydrophilic polymer 1 / E2000 / BN-77 of 100 / 400 / 40. This mixture was adjusted so that the total solid content concentration of the resin components (hydrophilic polymer 1, E2000, and BN-77) was 6.2% by mass and the mixing ratio (mass ratio) of acetone to water was 50 / 50, and the mixture was stirred for 1 hour to obtain a coating solution.

[0204] In Example 16, a lubricating layer (dry film thickness: 4 μm) was formed on the PVC intermediate layer in the same manner as in Example 16, except that the coating solution prepared above was used instead. This resulted in a wire (Sample 19) with a lubricating layer formed on the PVC intermediate layer containing hydrophilic polymers 1, E2000, and BN-77 in a mixing ratio of 100 / 400 / 40.

[0205] Example 20 A hydrophilic polymer 1 was obtained in the same manner as in Example 1.

[0206] The hydrophilic polymer 1, polyurethane E2000, and elastron BN-77 obtained above were mixed in a mass ratio (solids ratio) of hydrophilic polymer 1 / E2000 / BN-77 of 100 / 400 / 60. This mixture was adjusted so that the total solids concentration of the resin components (hydrophilic polymer 1, E2000, and BN-77) was 6.2% by mass and the mixing ratio (mass ratio) of acetone to water was 50 / 50, and the mixture was stirred for 1 hour to obtain a coating solution.

[0207] In Example 16, a lubricating layer (dry film thickness: 4 μm) was formed on the PVC intermediate layer in the same manner as in Example 16, except that the coating solution prepared above was used instead. This resulted in a wire (Sample 20) with a lubricating layer formed on the PVC intermediate layer containing hydrophilic polymers 1, E2000, and BN-77 in a mixing ratio of 100 / 400 / 60.

[0208] Example 21 A hydrophilic polymer 1 was obtained in the same manner as in Example 1.

[0209] The hydrophilic polymer 1, polyurethane E2000, and elastron BN-77 obtained above were mixed in a mass ratio (solid content ratio) of hydrophilic polymer 1 / E2000 / BN-77 of 100 / 400 / 80. This mixture was adjusted so that the total solid content concentration of the resin components (hydrophilic polymer 1, E2000, and BN-77) was 6.2% by mass and the mixing ratio (mass ratio) of acetone to water was 50 / 50, and the mixture was stirred for 1 hour to obtain a coating solution.

[0210] In Example 16, a lubricating layer (dry film thickness: 4 μm) was formed on the PVC intermediate layer in the same manner as in Example 16, except that the coating solution prepared above was used instead. This resulted in a wire (Sample 21) with a lubricating layer formed on the PVC intermediate layer containing hydrophilic polymers 1, E2000, and BN-77 in a mixing ratio of 100 / 400 / 80.

[0211] For Samples 17 to 21 obtained in Examples 17 to 21, the sliding durability of the lubricating layer was evaluated according to the method and criteria described in the above [Sliding Durability Evaluation 2]. Further, for Samples 17 to 21 obtained in Examples 17 to 21, the tip abutment resistance was evaluated according to the method and criteria described in the above [Tip Abutment Resistance Evaluation]. The results are shown in Table 6 below.

[0212] [Fine Particle Test] To examine the effect of adding polyisocyanate, for Samples 16 to 21 of the above Examples 16 to 21, the generation of fine particles under more severe conditions was evaluated using the test system shown in Figure 6 according to the following method.

[0213] The test system 60 shown in Figure 6 has a mold 63 with a total length of 450 mm and an inner diameter of 3 mm, which is bent by providing three wavy bent portions at an angle of about 80° with a curvature radius of 15 mm. A 4Fr catheter tube 62 of 100 cm or more is set in this mold 63. 100 mL of distilled water is injected from the hub 61 of the catheter, the liquid discharged from the catheter tip is collected, and this is used as a blank liquid.

[0214] Next, each sample is set in the catheter tube 62 filled with distilled water, and is caused to reciprocate (slide) 10 times at a sliding distance (stroke) of 100 cm. After sliding a predetermined number of times, the sample is taken out from the catheter tube 62, 100 mL of distilled water is injected into the catheter tube 62, and the sample liquid discharged from the catheter tip is collected.

[0215] The number of fine particles of 10 μm size (diameter) or larger in the sample liquid and blank liquid (100 mL each) collected above was measured with a liquid particle counter (manufactured by HIAC, device name: light-shielding automatic fine particle measuring apparatus), and the value obtained by subtracting the measured number of fine particles in the blank liquid (Y0 particles) from the number of fine particles in the sample liquid (Y1 particles) (=Y1-Y0 (particles)) was defined as the number of fine particles of the test sample.

[0216] As a result, the number of particles in samples 16-21 was sufficiently low in both cases. Furthermore, the ratio of the number of particles in samples 17-21 to the number of particles in sample 16 (= number of particles in each sample / number of particles in sample 16) was calculated, and the results ("particle number ratio" in the table below) are shown in Table 6.

[0217] [Table 6]

[0218] The results in Table 6 show that the number of particulate matter decreases with further addition of polyisocyanate. This result is presumed to be due to an increase in the film strength of the surface lubrication layer. Furthermore, these results suggest that using polyisocyanate can provide superior lubricity and lubrication retention (sliding durability) even under more severe conditions.

[0219] This application is based on Japanese Patent Application No. 2021-107517, filed on 29 June 2021, the disclosures of which are referenced and incorporated in whole. [Explanation of Symbols]

[0220] 1...Water, 2... Petri dish, 3… Sample (medical device), 4... Terminals, 5... Load, 6... Mobile table, 10...Friction measuring machine, 30…Ni-Ti wire, 31...tip, 32...the straight tip, 33... Tapered section, 34...rear end, 40...Micro load cell, 42... Load cell, 43... Sample, 44... Sample chuck section, 46... Foundation, 51...Main pipe, 52...side branch, 53...Curved section, 54...Straight section, 50... Vascular model, 61... Hub, 62... Catheter tube, 63... type, 60... Examination-related, 101...Base material layer, 101a...Base layer core section, 101b...base material surface layer, 102…Surface lubricant layer, 100... Medical devices.

Claims

1. A medical device comprising a base layer and a surface lubricating layer formed on at least a portion of the base layer, The surface lubricating layer comprises a polymer having a carboxyl group or a salt thereof and polyurethane. The polyurethane has an elongation rate of 700% or more and a Young's modulus of 5.0 N / mm². 2 That concludes the medical device description.

2. The medical device according to claim 1, wherein the polyurethane is contained in the surface lubricating layer in a proportion of 50 to 1200 parts by mass per 100 parts by mass of the polymer.

3. The medical device according to claim 2, wherein the polyurethane is contained in the surface lubricating layer in a ratio of 100 to 1000 parts by mass per 100 parts by mass of the polymer.

4. The medical device according to claim 1 or 2, wherein the polymer is at least one selected from the group consisting of hyaluronic acid or its alkali metal salt or group 2 metal salt, polyacrylic acid or its alkali metal salt or group 2 metal salt, and polymers having a structural unit represented by the following formula (1). 【Chemistry 1】 In the formula, X 1 and X 2 One of the components is sodium or potassium, and the other is a linear or branched alkyl group having 1 to 3 carbon atoms.

5. The medical device according to claim 1 or 2, wherein the surface lubricating layer further comprises a polyisocyanate or a crosslinked product thereof.

6. The medical device according to claim 1 or 2, wherein the medical device is a catheter or a guidewire.

7. The elongation rate is 700% or more, and the Young's modulus is 5.0 N / mm 2 Prepare or select polyurethane that meets the above criteria; A coating solution is prepared containing the polyurethane and a polymer having a carboxyl group or a salt thereof. A method for manufacturing a medical device, comprising applying the coating liquid to a substrate layer to form a surface lubricating layer on the substrate layer.

Citation Information

Patent Citations

  • Stent and its production method

    JP2006141555A

  • Extensibility organic base material

    JP2013166838A

  • Homogeneous film composition

    JP2017519854A

  • Medical instrument and method for manufacturing same

    WO2015029625A1

  • Medical instrument

    WO2021054359A1